Examination of a short-term underwater soundscape in a southeast Chinese Bay - Xuming Peng; Hao Wu; Siguang Liu; Fuxing Wu; Weijie Fu; Fei Zhang; Wenjie Xiang; Wenzhan Ou; Boyu Zhang; Jiayin Wang; Chao Long; Zhongchang Song (Marine Pollution Bulletin, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Biochar-assisted rapid formation of core–biofilm anammox granules via interfacial trapping of extracellular polymeric substances - Jingwei Fu; Yue Li; Yaqian Liu; Can Xiong; Pei Li; Xuanqi Long; Qian Li; Rong Chen (Bioresource Technology, 2026)

Quantitative evaluation of ground disturbance induced by shield tunneling considering soil spatial variability: insights from field monitoring and random finite element analysis - Zhang Hao; Xue Wen-bin; Zhu Lei; Liu Jin-long; Ma Liu-fu; Xiong Feng; Li Peng-fei; Tannant Dwayne (Tunnelling and Underground Space Technology, 2026)

Erratum to “Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.)” [Postharv. Biol. Technol. 240 (2026) 114463] - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Interface electronic Coupling-Migration and morphology control in NiMnSe Heterostructure: Synergistic sulfur doping and vacancy engineering for efficient water splitting and supercapacitors - Zhiwei Lu; Rao Fu; Xi Peng; Xiangyi Long; Yue Zhang; Yidian Yuan; Qiule Lu; Li Zhang; Minglei Yan; Jianshan Ye; Lan Zhang (Fuel, 2026)

Fluorine-doped PBA@FPO core-shell structure as bifunctional electrocatalyst for overall water splitting through electronic engineering synergy - Zhiwei Lu; Ke Chen; Rao Fu; Xiangyi Long; Peixin Jiang; Jinrui Wu; Yue Zhang; Yidian Yuan; Qiule Lu; Zhaodan Fu; Minglei Yan; Lan Zhang (Fuel, 2026)

Influence mechanism of tritium exposure on the growth and microcystin synthesis of Microcystis aeruginosa under rising temperature - Xue Gong; Xin-wen Zhang; Ling-shu Xu; Chuan-dong Wang; Bao Zhang; Qian Fu; Qi-lin Dai; Jin-long Lai (Environmental Pollution, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Constructing a “switch” for photo-thermal catalytic pathway: Directional regulation of NO reduction product distribution by the coordination mode at the La site over Pd–La/CeO2 - Jianfei Li; Boxiang Du; Qian Xia; Zhuoran Bi; Xiangyu Meng; Jinlin Long; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2026)

Assessing the cardiovascular toxicity of aspartame: An integrated approach from computational prediction to experimental validation - Qiuhe Chen; Hongjing You; Hecai Wang; Xuanchen Guan; Xiujuan Cen; Lanting Fu; Liang Long; Ke Wang; Yue Xu; Yang Chen (Chemico-Biological Interactions, 2026)

Targeted emission controls for ozone pollution mitigation based on mesoscale weather pattern classifications in China’s Pearl River Delta region - Aoxing Zhang; Jiongkai Chen; Huiran Feng; Wei Tao; Jiajia Mo; Wenlu Wu; Jianfeng Guo; Tianle Sun; Long Yun; Min Yan; Xiaolin Wang; Tzung-May Fu (ENGINEERING Environment, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.) - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

A salt-tolerant dual-network hydrogel based on tea waste biochar for efficient seawater desalination - Kun-Xiu Liu; Yi-Bin Li; Lei Xu; Cai-Hua Liu; Zhu-Long Yu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Journal of Environmental Chemical Engineering, 2026)

From area amplification to area retention: Carbon-sheathed bismuth nanoflowers for mechanistically durable vanadium redox flow batteries - Enkang Fu; Xiaoyu Huo; Mingcong Tang; Yuran Bai; Xin Long; Xusong Gong; Xingyi Shi; Liang An (Chemical Engineering Journal, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

A quasi-eutectic electrolyte strategy regulating chemical bond strength endows promoted ion-decoupled kinetics for high-performance aluminum-ion batteries - Wenpeng Cao; Yongde Long; Pengcheng Liu; Mingming Xie; Jinhua Luo; Kai Du; Chengjie Wang; Jingzhen Li; Jing Geng; Hanguang Fu; Yuxiang Hu (Chemical Engineering Journal, 2026)

Homogeneous covalent internal plasticization of high-amylose starch via post-gelatinization hydroxypropylation: Critical substitution threshold for ductility and anti-retrogradation - Jun Fu; Qingfei Duan; Yiwen Yang; Xinyi Dong; Yuanyuan Li; Fengwei Xie; Long Yu (Carbohydrate Polymers, 2026)

EXtreme Gradient Boosting for Lithology Identification with Well Logs: A Case Study from the Salt Lake Area, Eastern Qaidam Basin, China - Zhong-yi Duan; Fu-long Zheng; Hang-yu Yue; Jia-pan Yan; Kun Xiao; Ting-yan Zhang; Jia-dong Yan (Applied Geophysics, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

From thermal runaway propagation to inhalation risk: Influence of state of charge on heat transfer and particle emissions in lithium-ion batteries - Yijia He; Qiang Dong; Zhan Wang; Huifeng Li; Chenwei Shang; Long Ma; Ming Fu; Jinlong Zhao; Xiaole Zhang (Process Safety and Environmental Protection, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

Molecular-level insights into the disinfection by-product precursor removal by biological activated carbon process using FT-ICR MS - Guojing Shi; Quan Gao; Qing-Long Fu; Huang Huang; Xin Yang (Journal of Environmental Sciences, 2026)

Improving the flavor and quality of roasted mackerel (Pneumatophorus japonicus) via sous-vide cooking: Tracking the dynamics of key volatile compounds - Hui Liu; Tai-yu Li; Wei-yi Xu; Yong-jie Long; Yan-wei Yuan; Jing-jing Fu; Jian-zhong Han; Yue-wen Chen; Wen-qiang Cai (Food Chemistry, 2026)

Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Modeled spatial structures of medical resource allocation in China's urban agglomerations: Comparative advantage, potential intercity interaction, and the medical consortiums reform - Yunlong Suo; Rou Zhang; Chengxu Long; Zhanchun Feng; Qian Fu (Applied Geography, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A pulsar escaping an ancient open cluster via tidal stripping - Lei Zhang; Xiaoting Fu; Di Li; Emma Carli; Long Wang; Jiaqi Zhao; Craig O. Heinke; Emanuele Dalessandro; Yang Chen; Angela Bragaglia; Duncan R. Lorimer; Ewan D. Barr; et al. (Science Bulletin, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Preferentially selective lithium recovery from spent lithium-ion battery leachates using NaBPh4/TBP synergistic extraction - Qian Cheng; Yue Wang; Yongxiang Wang; Panfeng Gao; Jun-Tao Li; Jiangxue Long; Haiyan Fu (Hydrometallurgy, 2026)

Quantitative criteria and deformation-dependent model for passive soil arching in compacted clay - Xiao-Hu Zhang; Han-Lin Wang; Xiang-Shen Fu; Cheng-Shuang Yin; Meng-Cheng Long (Computers and Geotechnics, 2026)

GAS6 Mediates Benzo[a]pyrene-Induced Pathological Cardiac Hypertrophy via the mTOR/HIF-1α Glycolytic Remodeling Axis - Guangming Li; Feihu Long; Zhiyue Liu; Jiarui Nicole Fu; Yuanyin Teng; Shanshan Cai; Xiaoling Zhang; Yingji Wang (Chemico-Biological Interactions, 2026)

Cardiovascular toxicity of ethyl maltol exposure: a comprehensive investigation from virtual screening to experimental validation - Qiuhe Chen; Lanting Fu; Hecai Wang; Xiujuan cen; Liang Long; Hongjing You; Qimeng Tan; Xinyue Chen; Yuhao Liu; Haiyan Li; Yue Xu; Yang Chen (Archives of Toxicology, 2026)

Dynamic source apportionment of heavy metals in Bohai Bay sediments using a temporally hierarchical PCA-APCS-HBM model - Qiulian Wang; Long Han; Tong Han; Zhenchao Fu; Zeli Li; Han Ding (Marine Pollution Bulletin, 2026)

Regional-scale prediction and assessment of soil organic matter content in the Yuanmou Dry-Hot Valley, Southwest China, using satellite-derived phenological time series and deep learning - Dengdeng Ding; Jida Yang; Sihe Deng; Hongye Zhu; Zhengbo Ma; Chengxiu Fu; Junlang Deng; Dingyun Zhao; Zhen Long; Xiaoyan Wang; Peiwen Yang; Qibin Chen; et al. (Environmental Monitoring and Assessment, 2026)

Climate warming and sulfide exposure jointly disrupt intestinal microbiota and barrier homeostasis in the freshwater crab Eriocheir sinensis - Yi-fu Xing; Jian Tian; Xuan-yi Zhu; Yi-fan Feng; Qi-bin Zhu; Long-long Fu; Jia-xin Yang (Aquaculture, 2026)

DEM modelling of tillered wheat plants with dynamic parameter calibration for high-speed cutting simulation - Kai Sun; Jianqun Yu; Jun Fu; Yajun Yu; Jinwen Zhao; Long Zhou; Yang Wang (Biosystems Engineering, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Multi-omics identifies key genes regulating intramuscular metabolites to affect age- and gender-specific meat quality in sheep - Yali Song; Tianshu Dai; Shijie Tang; Zehu Yuan; Fadi Li; Weiwei Fu; Long Guo; Xueying Zhang; Xiangpeng Yue (Food Bioscience, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Visualization on deformation characteristics of passive soil arching effect in unsaturated compacted clay under plane-strain condition - Xiao-Hu Zhang; Han-Lin Wang; Meng-Cheng Long; Zhen-Nan Tian; Xiang-Shen Fu; Cheng-Shuang Yin (Bulletin of Engineering Geology and the Environment, 2026)

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Clay minerals reduced antibiotic resistance gene dissemination in the plant rhizosphere through inhibiting horizontal gene transfer and reshaping microbial community structure - Yuxin Qin; Yuqiu Luo; Haihui Fu; Haopeng Pang; Xiaoyu Long; Qian Zhang; Hai Lin; Bing Li (Journal of Environmental Chemical Engineering, 2026)

Transformation and transport: Polyvinyl chloride microplastics modulate fipronil accumulation and toxicity in zebrafish - Long Fu; Jing Yu; Kunting Li; Peibin Xu; Keran Xu; Lei Mai; Dali Wang; Huizhen Li; Jing You; Eddy Y. Zeng (Journal of Environmental Sciences, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Revealing the chemical differences and their application on geographical origin and aging year identification of Artemisia Argyi Folium based on GC–MS and UHPLC-HRMS untargeted metabolomics - Kangyan Zhang; Siyu Wang; Huiru Zhang; Jing Ming; Wanjun Long; Haiyan Fu (Food Research International, 2026)

On-demand amorphous calcium phosphate-mediated regeneration of dentin and enamel using ion-regulated hydroxypropyl methylcellulose and carboxymethyl chitosan hydrogels - Zihan Cui; Zhiwen Liu; Zhixin Zhang; Danni Wang; Taoyu Chen; Baiping Fu; Ling Zhu; Long Zhao; Zhe Wang (Carbohydrate Polymers, 2026)

Bulk and single-cell transcriptome analyses combined with molecular simulations identify ferritinophagy as a key target for resveratrol in osteoarthritis - Xingqian Fu; Wei Liu; Yongxiang Zhang; Qihong Wu; Gang Long; Yifa Zhai; Chao Song; Po Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Daphnetin prevents acute graft-versus-host disease by suppressing donor T cell expansion and function - Zhi-Feng Wei; Yan-Fang Chen; Fei Song; Yu Fu; Yun-Wei Zhang; Tian-Xue Qin; Su-Jun Gao; Long Su (Inflammopharmacology, 2026)

Fish community and its relationships with environmental factors in the Jiupan River, a secondary tributary of the Three Gorges Reservoir - Junquan Ren; Zhenxin Chen; Kaiyang Wu; Lilong Chen; Rongchao He; Mengqiao Long; Yankun Shen; Hanlin Wang; Mei Fu; Hongjian Lv; Weizhi Yao (Environmental Biology of Fishes, 2026)

Iron plaque crystallinity driven by phosphorus gradients directs Cd/As partitioning in rice - Jibo Long; Qian Zhu; Hongyu Fu; Bingyu Li; Yimin Zhou; Zhuoqing Li; Jiaxiang Wang; Cheng Qiu; Qinghai Liu; Ming Lei (Cereal Research Communications, 2026)

Kinetic Modelling of the Decay of Respiratory Syncytial Viruses (RSV) Facilitated a Robust Wastewater-Based Surveillance for RSV - Yuqing Long; Jiayi Liu; Xiuyuan Shi; Xueling Yang; Yongyan Long; Jinzhou Xiao; Xinxin Han; Songzhe Fu (Food and Environmental Virology, 2026)

Nighttime Atmospheric Pressure Measurement at 80–110 km Altitude over Xi’an by GBAVTII - Cun-Xia Li; Yang-He Liu; Yan Fang; Ning-Ju Hui; Yan-Long Wang; Yi-Shan Zhang; Di-Di Fu; Yuan-He Tang (Applied Geophysics, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Oxime ester–linked N-phenylphthalimide derivatives as PPO inhibitors: structure–activity relationships, herbicidal activity, crop selectivity, and in silico safety assessment - Xian-Ming Zhang; Yue-Li Zou; Ya Jiang; Si-Yi Yao; Shuang Gao; Li-Xia Zhao; Yu-Long Liu; Ying Fu (Pesticide Biochemistry and Physiology, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Grain-size-specific Sr–Nd isotopic evidence for the dominant role of fluvial sediments in Danube loess formation - Xuechao Wu; Qingzhen Hao; Slobodan B. Marković; Xinbo Gao; Long Han; Yu Fu; Yang Song; Zhipeng Wu; Shouye Yang; Zhengtang Guo (Geochimica et Cosmochimica Acta, 2026)

Kinetic analysis of adsorption-hydration hybrid CH4 storage in mesoporous ZIF-8@AC: Study on the synergistic characteristics of temperature, CH4/H2O transport and hydrate growth - Qilin Han; Long Zheng; Shujun Chen; Yue Fu; Huimin Duan; Hongbo Zhao; Jinliang Liu (Gas Science and Engineering, 2026)

Suppression of lipid oxidation in frozen unwashed surimi by polyphenols-extract of foods: Investigating the synergistic mechanism of targeting hemoglobin and key radical-producing enzymes - Guiyuan Xiang; Jiangtao Li; Zhao Long; Jianan Zhang; Xiangjin Fu; Tianqing Lan; Kangzi Ren; Amna Jabeen (Food Bioscience, 2026)

Oral delivery of colon targeted zein-xanthan gum nanoparticles loaded with giant salamander Maillard hydrolyzed peptide: improving ulcerative colitis by regulating the production of antioxidant peptides in digestive products - Jing-Jing Fu; Fan-Yu He; Yong-Jie Long; Wen-Qiang Cai; Jun-Xin Wu; Yue-Wen Chen (Food Bioscience, 2026)

Source-oriented probabilistic human health risk assessments and priority heavy metal pollution control areas identification in the Laoguan river basin - Xinxin Long; Changyv Zhou; Hui Fu; Shaokang Meng; Yuan Wei (Environmental Pollution, 2026)

Enzyme mimics catalytic process in organic pollutants treatment: Applications, mechanisms, and challenges - Ting Peng; Sha Long; Enxu Liu; Xuran Liu; Dongbo Wang; Yukui Fu; Jin Huang (Chemical Engineering Journal, 2026)

A bipolar membrane-driven proton self-supply strategy for the sustained and efficient electrosynthesis of Na2S2O4 from desulfurization byproduct - Yingxue Fu; Jun Wu; Hao Chen; Lin Wu; Zhujiang Wang; Yelin Zhu; Jiaqi Long; Zhipeng Tang; Fenghua Shen; Kaisong Xiang; Hui Liu (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Dual-crosslinked polysaccharide microspheres via glycated collagen and sodium alginate/chitosan for intestine targeted delivery of curcumin in ulcerative colitis treatment - Jing-jing Fu; Si-yi Mei; Yong-qiang Chen; Xiang-yu Fu; Yong-jie Long; Jun-xin Wu; Wen-qiang Cai; Yue-wen Chen (Carbohydrate Polymers, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Comprehensive Comparison on Potentially Toxic Elements Between Sandstorm PM2.5 and Haze PM2.5 - Jiaojiao Xie; Yixian Long; Songyao Liu; Yiran Fu; Chun-Gang Yuan; Mingyu Li; Shuang Deng (Asia-Pacific Journal of Atmospheric Sciences, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

A spectral multiaxial fatigue reliability approach for riser girth welds based on the master S-N curve - Long Zhang; Tianfeng Zhao; Yuxiang Yang; Chao Fu; Jiatong Ling; Depeng Liu (Ocean Engineering, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Enhanced pollutant removal via polybutylene succinate-based microbial-agent biofilm process: Optimizing heterotrophic nitrification–aerobic denitrification technology for low-carbon wastewater treatment - Qian Zhang; Zheng Chen; Kun Long; Bixiang Nie; Fu Wei; Lin Deng; Siyu Hua (Journal of Environmental Chemical Engineering, 2026)

Thallium isotope insights into Mn Oxides as precursor to Ediacaran Mn Carbonate Ore - Xuwen Luo; Haifeng Fan; Jean Clemente; Chao Li; Hongjie Zhang; Long Chen; Yaowen Wu; Shaohong Fu; Jianfeng Gao; Hanjie Wen; Sune G. Nielsen (Geochimica et Cosmochimica Acta, 2026)

A comprehensive review on wine authentication and traceability: Current issues, solutions and future perspectives - Hai-Qing Qiang; Hui-Wen Gu; Xiao-Li Yin; Zhan Meng; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Novel dual-phase porous Mn2O3/(Co,Mn)(Co,Mn)2O4 composite cathode material with enhanced interfacial stability for ultra-long cycle life in zinc ion batteries - Haoran Wang; Zhaoxia Hou; Hui Zhang; Wensheng Zong; Shuting Yin; Haibo Long; Zhongchao Fu; Nan Wu; Zihui Zhai; Depeng Zhang; Fanshun Meng; Dan Zhou (Chemical Engineering Journal, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

Chemodiversity of Dissolved Organic Matter in Groundwater Elucidated by the Ultrahigh-Resolution Mass Spectrometry: A Case Study of the Jianghan Plain, China - Jingjing Sun; Ying Liang; Qing-Long Fu (Journal of Earth Science, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Smartphone app-enabled dual-mode fluorescence and colorimetric portable sensors using RB@BSA-AuNRs for quality identification of plant-derived products - Hengye Chen; Xueqing Zeng; Guanghua Lei; Yun Huang; Wanjun Long; Wei Lan; Yuting Guan; Haiyan Fu (Food Research International, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

PRSGNet: A robust framework for crop row detection in complex field scenarios - Dengbin Fu; Yinghu Cai; Zhanpeng Liang; Zhenyu Tang; Zhiqiang Yao; Hao Gong; Renjun Hu; Jiating Li; Long Qi (Computers and Electronics in Agriculture, 2026)

Optimizing environmental surveillance for early detection of zoonotic pathogens via fecal shedding modeling - Xin Du; Zhiqiang Deng; Yuqing Long; Fenglan He; Chunlong Zhu; Chun Han; Hui Li; Songzhe Fu (Water Research, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Multiscale insights of interfacial transport and kinetics in acidic CO2 electroreduction - Hang Wang; Yang Wang; Jian Wang; Zhaojian Liang; Long Ma; Chuanjun Wang; Xun Zhu; Jun Li; Qian Fu; Qiang Liao (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Metabolomic remodeling and genetic regulation in potato tubers during domestication - Zhong Zhang; Wei Tan; Jintao Liu; Jiangyue Long; Zefeng Zhai; Yang Feng; Lingling Wei; Hui Du; Qi Fu; Yanan Pu; Pei Wang; Chunzhi Zhang; et al. (Molecular Plant, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Centrifuge model study on the influence of PVD installation depth under surcharge preloading - Jun Wang; Chenglong Gu; Hongtao Fu; Long Wang; Junfeng Ni; Ziyang Gao; Xueyu Geng (Geotextiles and Geomembranes, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

A novel bacteriophage pAEh1 for controlling Aeromonas hydrophila infection in aquaculture - Sifan Jiang; Boyang Zhou; Tongping Zhang; Rongsi Dai; Su Long; Linlin Yang; Mingwang He; YanJiao Fu; Jiajing Guo; Zhipeng Gao (Fish & Shellfish Immunology, 2026)

Multiscale-reinforced high-strength MXene-based EMI shielding films with integrated electronic skin functionalities - Lingfeng Yu; Yanni Yang; Xinyu Huang; Yihao Xiao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China [Aquaculture Volume 609, July 2025.] - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Maize adaptation to low-dose nanoplastic–lead co-contamination: Foliar metabolic reprogramming and phyllospheric microbiome restructuring - Qian Fu; Jin-sheng Shi; Jin-long Lai; Yu Zhang; Yan Huang; Xue-gang Luo (NanoImpact, 2026)

Spatial distribution, source, and ecological risk of organochlorine pesticides (OCPs) in the Yellow and Bohai Seas - Long-Kun Sun; Jie Fu; Ming-Liang Zhao; Wen-Qing Wang; Zhen He; Gui-Peng Yang (Marine Environmental Research, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Degradation of organic refractory contaminants by phosphate buffer activated peroxymonosulfate: The overlooked roles of oxygen reactive species - Qing Liu; Siying Long; Xiaodi Duan; Qiqi Zhu; Qing Fu; Wei Wang; Jiarui Shi; Yaqi Wang; Chun Cai (Journal of Cleaner Production, 2026)

Mechanisms of uranium and cadmium Co-contamination on rhizosphere microecology and accumulation in sweet potato varieties - Jin-long Lai; Xue Gong; Qian Fu; Xue-gang Luo (Journal of Environmental Radioactivity, 2026)

Corrigendum to “Current trends and advanced techniques for Chinese green tea authenticity verification: A thorough review” [Food Res. Int. 222 (2025) 117748] - Huiru Zhang; Siyu Wang; Kangyan Zhang; Hengye Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2026)

Comparison of pork quality and colon microbiota composition in Crossbred Pigs from Different Duroc × (Landrace × Yorkshire) pigs - Yiyan Liao; Dongfang Wang; Yan Fu; Yongqi He; Jianlan Wang; Jianzhuang Tan; Long Pan; Yong Su (Food Bioscience, 2026)

Promotion of nitric oxide to ammonia via nickel species enhanced active hydrogen generation - Hui Liu; Lin Wu; Yingxue Fu; Zhujiang Wang; Jiaqi Long; Jing Yuan; Xinlei Wang; Jieyu Li; Jun Wu; Kaisong Xiang (Chemical Engineering Journal, 2026)

Secukinumab improves pregnancy outcomes in recurrent spontaneous abortion with T helper 17 cells/T regulatory cells imbalance: a retrospective cohort study - Guihua Zhu; Xue Wang; Shuqin Bi; Juan Liu; Guiling Yuan; Ning Li; Jinhua Fu; Long Zhao (European Journal of Clinical Pharmacology, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Pore Structure Evolution in Marine Sands Under Laterally Constrained Axial Loading - Xia-Tao Zhang; Cheng-Liang Ji; Le-Le Liu; Hui-Long Ma; Deng-Feng Fu (Journal of Marine Science and Engineering, 2025)
Installation in sand is sensitive to its evolving pore structure, yet design models rarely update permeability for real-time fabric changes. This study tracks the stress-dependent pore size distribution of coarse sand under laterally constrained compression using high-resolution X-ray nano-CT. Scans taken at six axial stress levels show that the distribution shifts toward smaller radii while keeping its log-normal shape. A single shifting factor, defined as the current median radius normalized by the initial value, captures this translation. The factor decays with axial stress according to a power law, and the exponent as well as the reference pressure are calibrated from void ratio data. The resulting closed-form expression links mean effective stress to pore radius statistics without extra fitting once the compressibility constants are known. This quantitative relation between effective stress and pore size distribution has great potential to be embedded into coupled hydro-mechanical solvers, enabling engineers to refresh hydraulic permeability at every computation step, improving predictions of excess pore pressure and soil resistance during suction anchor penetration for floating wind foundations.

Using UAV multispectral image data to monitor the nitrogen status of head cabbage shoots in the Liupan Mountain area of China - Shuai Wang; Long-Guo Wu; Hua Ma; Kelsang Choron; Fu-Shun Zheng; Zhong-Ting Song; Cui Yin; Hong-Yan Zhu; Peng-Yuan Lv; Yun-e Cao (International Journal of Remote Sensing, 2025)

Tassel counting of individual ridge from UAV RGB imagery based on YOLOv8m with deep SORT and double-step Otsu thresholding algorithm by filtering abnormal IDs for maize breeding - Man Xia; Leilei He; Yu Gu; Xiaojuan Liu; Bryan Gilbert Murengami; Lamin L. Janneh; Rui Li; Yan Long; Anastasia Grecheneva; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Dynamic development of global contiguous flash droughts: from an event-based spatiotemporal perspective - Dingkui Wang; Xuezhi Tan; Xinxin Wu; Zeqin Huang; Simin Deng; Yaxin Liu; Jianyu Fu; Xuejin Tan; Xitian Cai; Bingjun Liu; Haiyun Shi; Long Yang; et al. (Journal of Hydrology, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Experimental analysis of the influence of drainage board diameter coefficient on sludge treatment combining horizontal drain-vacuum preloading with geomembrane bags - Jun Wang; Chenglong Gu; Xiaobing Li; Hongtao Fu; Junfeng Ni; Ziyang Gao; Long Wang (Geotextiles and Geomembranes, 2025)

Current trends and advanced techniques for Chinese green tea authenticity verification: A thorough review - Huiru Zhang; Siyu Wang; Kangyan Zhang; Hengye Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2025)

Recent advances in the applications of Bacillus subtilis in the fermentation of food: Improving product quality and enhancing biological activity - Xin Gao; Ruifeng Fan; Long Tan; Jiaqi Fu (Food Research International, 2025)

Comparative analysis of flavour profiles in cooking liquids from razor clams (Solen grandis) processed by different methods - Yujun Liu; Long Li; Di Yu; Pengfei Jiang; Xinrui Yang; Zhiyu Fu; Yongan Bai; Xiangfeng Liu; Qingzhi Wang; Hai Chi; Zhiyuan Song; Jie Zheng (Food Chemistry, 2025)

Harpadon nehereus Peptide FF4 alleviates hyperuricemia by regulating uric acid synthetase and transporters, as well as modulating the ROS/NLRP3 signaling pathway - Yang-na Huang; Hui-wen Zheng; Sheng-xiang Zhao; Zhan-ying Zhu; Yong-jie Long; Yue-wen Chen; Jing-jing Fu (Food Bioscience, 2025)

Potassium and phosphorus co-doped g-C3N4 with improved carrier migration for efficient photocatalytic degradation of 2,4-dichlorophenoxyacetic acid under visible light - Shan Liu; Simin Long; Yi Zhao; Zhonglin Chen; Jimin Shen; Gang Fu; Jiaxu Zhang; Jing Kang (Environmental Research, 2025)

Task-specific deep eutectic solvents: Intelligent molecular design for on-demand CO2 capture and release - Xuanang Fu; Huajie Qiu; Anteng Dai; Qinghai Long; Chao Liu; Zuoming Zhou; Guohua Jing; Bihong Lv (Chemical Engineering Journal, 2025)

Dynamic structural reconstruction of CuO under reaction conditions enhances photocatalytic activity in C H bond functionalization - Shaohui Zhang; Jia Liu; Yan Pu; Yifang Zhang; Yingcong Wei; Huaxiang Lin; Jinlin Long; Rongjian Sa; Xianzhi Fu; Rusheng Yuan (Chemical Engineering Journal, 2025)

Polydopamine-Ag engineered BaTiO₃ core-double-shells nanohybrids in PDMS composites for synergistically enhanced triboelectric output and antibiosis in self-sustaining wearables - Haiyan Fu; Lei Liu; Wei Liu; Zuchang Long; Ping Huang; Kai Fu; Hui Ou; Linmin Hu; Minhao Liao; Jianliang Gong (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Hydrophilic anions for expanding the electrochemical stability window of water-in-salt electrolytes - Jianglin Fu; Xuzhe Li; Yubing Li; Yu Li; Ziyue Yu; Liming Lei; Shuaikai Xu; Tangming Mo; Yu Long (Chemical Engineering Journal, 2025)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Stretching a single sugar chain - Yun-Long Chen; Chen-Chen Zheng; Fu-Jia Tian; Tai-Lang Yin; Xing-Hua Zhang (Carbohydrate Polymers, 2025)

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Applying natural product repurposing strategy to identify baicalein as novel caseinolytic protease P inhibitor and its application in the treatment of rice bacterial diseases - Zhaoju Sun; Teng Yang; Zhouqing Long; Xichun Fu; Jiao Meng; Xiang Zhou; Cai-Guang Yang; Song Yang (Pesticide Biochemistry and Physiology, 2025)

Investigating air-cushion effect in water-entry impact of notched-head blunt vehicles via the CFD-FEM coupling method - Zhe Zhang; Na-Na Yang; Wei Yang; Jin-Long Ju; Fu-Kui Gao; Wen-Hua Wu (Ocean Engineering, 2025)

Polybaric differentiation for arc magma genesis: a perspective from alumina saturation index - Peng Gao; Marcos García-Arias; William J. Collins; Long Chen; Hua Xiang; Hai-Ou Gu; Zi-Fu Zhao (Lithos, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

Smartphone-assisted colorimetric sensing hydrogels based on MnO2 NFs nanozyme for highly sensitive and rapid detection of tert-butylhydroquinone in edible oils - Xiaoyue Yue; Chenxu Hao; Long Fu; Chaoyun Wu; Yanhong Bai (Food Chemistry, 2025)

Evaluation of soil quality and system sustainability in ratoon rice paddy field under green manure application in central China - Ying Xu; Qiwen Hou; Jinbiao Xiang; Mutian Gao; Pufan Shao; Sheng Chen; Zhiqiang Fu; Pan Long; Cheng Huang (Field Crops Research, 2025)

Polychlorinated biphenyl pollution as an unintentional major contaminant in the Pearl River Delta, China - Hongbing Wang; Chenglong Wei; Guowei Fu; Daheng Zhang; Miao Fu; Junyi Jiang; Yue Long; Yanwei Song (Environmental Research, 2025)

Molecular characteristics of halogenated disinfection byproducts elucidated by Fourier transform ion cyclotron resonance mass spectrometry - Yiming Feng; Yifan Qian; Cun Liu; Qing-Long Fu (Environmental Pollution, 2025)

3D printed-assisted fabrication of embedded porous solar evaporators for efficient photothermal evaporation - Zhu-Long Yu; Lei Xu; Cai-Hua Liu; Wen-Bo Guo; Ming-Lai Fu; Baoling Yuan (Desalination, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

Optimization of conductivity and stability on inverse spinel CoFe2O4 for alkaline oxygen evolution reaction - Fu-Yu Guo; Jian Luan; Xian-Chen Meng; Peng Zheng; Wen-Long Duan; Wen-Ze Li (Chemical Engineering Journal, 2025)

Microphysics of warm season heavy precipitation in 2024 over China: A preliminary investigation based on FY-3G PMR observations - Long Wen; Zhaoyang Fu; Peiling Fu; Jiming Sun; Gang Chen (Atmospheric Research, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Warming alters the effects of roots and extramatrical mycelia on soil organic carbon and its composition in a Tibetan plateau swamp meadow - Xiaoxiang Zhao; Qiuxiang Tian; Anders Michelsen; Long Chen; Xiang Wang; Rudong Zhao; Lihua Fu; Kai Yang; Yan Yang; Feng Liu (Applied Soil Ecology, 2025)

Retraction notice to “Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation” [Chemosphere 357, June 2024, 142070] - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2025)

The novel model INEDM and two traditional models for estimating the carrying capacity of Hong Kong oyster (Crassostrea hongkongensis) in two aquaculture systems in Guangdong Province of China - Xing-Chi Guo; Wen-Ding Liu; Xiao-Yan Ye; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2025)

Research on rock breaking mechanism of laser-assisted TBM cutter based on continuous-discrete coupling method - Yukun Chen; Zhiqiang Huang; Kai Fu; Meng Yin; Long Li (Tunnelling and Underground Space Technology, 2025)

The surface nutrients in China's coastal waters in the winter of 2025 - Chaofeng Wang; Jiaxuan Ni; Xiaoyu Wang; Longwen Fu; Lilian Wen; Zhen Guo; Long Gao; Xinhua Chen; Jun Ma (Marine Environmental Research, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Experimental investigation into CO2 sequestration and associated ecological behaviours of carbon-negative backfilling with coal gangues - Baiyi Li; Kang Long; Wenbo Cheng; Xinghui Fu; Jiayuan Ma; Shuaijie Zhang (International Journal of Greenhouse Gas Control, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

Energy-efficient CO₂ capture using a biphasic tertiary-amine ionic liquid with reversible phase behavior - Qinghai Long; Yutao Bai; Anteng Dai; Huajie Qiu; Xuanang Fu; Xiaoyun Chen; Chao Liu; Waseem Hayat; Bihong Lv; Guohua Jing; Zuoming Zhou (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Nitrogen/boron co-doped carbon derived from coal liquefaction residue for capacitive energy storage - Xiaoxia Yang; Long Chen; Junjie Hui; Guoxiao Sun; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Wenlin Zhang; Feng Fu (Chemical Engineering Journal, 2025)

Microphysics and kinematics within the eyewall of Super Typhoon Yagi (2024) revealed by FY-3G PMR observations - Zhaoyang Fu; Jiming Sun; Peiling Fu; Long Wen; Gang Chen (Atmospheric Research, 2025)

Immune responses of Ctenopharyngodon idella juveniles against the ciliated parasite's reinfection induced by Ichthyophthirius multifiliis theronts at the threshold density - Ting-Long Hou; Yao-Wu Fu; Xing-Chi Guo; Shu-Guan Guo; Shi-Lu Huang; Qi-Zhong Zhang (Aquaculture, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Ribavirin showed insect growth regulator activity to Helicoverpa armigera - Li Xu; Yin Huang; Zezheng Liu; Qi Zuo; Minghui Long; Yichen Fu; Runqiang Liu; Yunchao Kan; Dongzhi Li (Journal of Asia-Pacific Entomology, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Storage evolution in non-volatile and volatile lipid oxidation products of salted large yellow croaker based on targeted lipidomics and GC–MS analysis - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Chemistry, 2025)

CO2 electroreduction in acidic zero-gap electrolyzers: A modeling-based quantitative assessment of electrochemical and energy characteristics - Yang Wang; Hang Wang; Zhongyin Kang; Zhisheng Long; Guifeng Zhou; Qian Fu; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2025)

An ionic liquid phase change absorbent capable of low-temperature regeneration: Investigation of phase change and regeneration mechanism - Huajie Qiu; Qinghai Long; Yutao Bai; Xuanang Fu; Chao Liu; Guohua Jing; Zuoming Zhou; Bihong Lv (Chemical Engineering Journal, 2025)

Building ultrathin nanosheet CeVO4/WO3·H2O Z-scheme heterojunction for boosting photocatalytic CO2 reduction - Chen Fu; Hongjiang Li; Jianing Jiang; Jinni Shen; Jinlin Long; Wenxin Dai; Xuxu Wang; Zizhong Zhang (Chemical Engineering Journal, 2025)

Aircraft Observations of Ice-Phase Microphysical Characteristics in Stratiform Clouds over the Qilian Mountains in Northwestern China - Yuyan Long; Tuanjie Hou; Baojun Chen; Shuangxi Fu; Rong Zhang; Shaofeng Hua; Yi Chang; Boyue Zhang (Advances in Atmospheric Sciences, 2025)

Design, synthesis, and mechanism study of novel isoquinoline derivatives containing an oxime moiety as antifungal agents - Yanxi Jin; Fu Chen; Ying Long; Jianeng Luo; Si Guo; LuYao Wang; Wei Chen (Molecular Diversity, 2025)

Accurate detection and high throughput profiling of unknown PFAS transformation products for elucidating degradation pathways - Bei Zhang; Jibao Liu; Shanshan Qing; Thilini Maheshika Herath; Huan Zhao; Supaporn Klabklaydee; Qing-Long Fu; Eunsang Kwon; Nozomi Takeuchi; Douyan Wang; Takao Namihira; Toshihiro Isobe; et al. (Water Research, 2025)

Improved identification of chlorinated disinfection byproducts by the sequential elution and absorption mode - Rong Qin; Yiming Feng; Shasha Zhuo; Qing-Long Fu (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

A nanozyme colorimetric sensor combined with cloud-based machine learning algorithm-assisted WeChat mini program for intelligent identification of Chinese green tea - Wanjun Long; Siyu Wang; Yangcheng Ling; Yuting Guan; Huiru Zhang; Hengye Chen; Wei Lan; Yuanbin She; Haiyan Fu (Food Research International, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

Achieving underpotential Mn deposition chemistry via hydrated eutectic electrolytes for aqueous manganese metal batteries - Quanhuan Yao; Linyang Li; Xue Chen; Shenghui Zhang; He Zhang; Yujie Fu; Cong Tian; Guilong Yan; Anjun Hu; Liujun Cao; Jianping Long (Chemical Engineering Journal, 2025)

Sequential hydrothermal liquefaction of lignocellulose-rich livestock manure: A new perspective on enhancing the production and quality of low-phenolic biocrude - Siyuan Long; Pengxin Yu; Jianrong Huang; Conghao Ku; Xinge Miao; Junjie Lan; Hao Fu; Chunbao Charles Xu; Haiwei Jiang; Zhengli Liu; Weiran Yang (Bioresource Technology, 2025)

Analysis of the response mechanism in lipid degradation of key gene LDH1 knockout strains of Saccharomyces cerevisiae under levulinic acid stress - Yulei Chen; Jiaye Tang; Qian Li; Wenli Xin; Ximeng Xiao; Borui Mou; Jialian Li; Fujia Lu; Chun Fu; Wencong Long; Hong Liao; Xuebing Han; et al. (Archives of Microbiology, 2025)

Development of an Ellipsoid Based Chart Datum Around the China Seas - Yanguang Fu; Yanxiong Liu; Mehdi Khaki; Fukai Peng; Xiaolong Mi; Yikai Feng; Xiaoli Deng; Long Yang; Qinghua Tang; Li Cui (Marine Geodesy, 2025)

Numerical investigation of aerated water entry by multiphase Riemann SPH method - Ke Zhao; Sheng-Fa Yang; Pei-Yin Yuan; Fu-Long Shi; Fu-Ren Ming (Ocean Engineering, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Smartphone app with cloud-based machine learning and visual sensor array for instrument-free detection of species, geographic origin, and quality marker in functional food Gancao - Yun Huang; Aifen Hu; Lixue Ren; WanJun Long; Wei Lan; Yi He; Yuanbin She; Hengye Chen; Haiyan Fu (Food Control, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Vegetation and climate history of the Tian Shan region of Xinjiang during the last millennium and their relations to past human civilization - Jian Huang; Fu‐long Yao (Journal of Quaternary Science, 2025)
The arid Central Asia has long demonstrated a correlation between human activity and climatic fluctuations, particularly during the Holocene. However, Late Holocene palaeoclimate records remain sparse, limiting our understanding of the dynamic relationship between climate variability and human civilization over the past millennium. This study based on peat sediment samples from the Zhaosu Basin on the northern slopes of the Western Tian Shan Mountains, China, reconstructs vegetation and climate changes over the past millennium by employing precise dating techniques and high‐resolution pollen analysis. The results were as follows: (1) grasslands have consistently dominated the northern slopes of the Western Tian Shan over the last millennium, as evidenced by the prevalence of pollen types, such as Artemisia , Chenopodiaceae, and Poaceae. During the Medieval Climate Anomaly (MCA, 1046–1288 ad ), frequently fluctuating Artemisia /Chenopodiaceae (A/C) ratios indicated a transition from warm–arid to warm–humid conditions. This trend shifted during the Little Ice Age (LIA, 1288–1476 ad ), marked by increased Picea pollen and positive principal component analysis axis 2 scores, suggesting a cooler and wetter environment. Pollen concentrations of arborvitae and shrubs peaked during the LIA (1476–1606 ad ), alongside high Picea content, signaling an intensified cold and wet climate. (2) Historical records correlate climate conditions with patterns of human habitation and development. The warm, humid climate during the MCA (1046–1288 ad ) coincided with the Song Dynasty, fostering population growth and cultural development on both slopes of the Tian Shan region. Conversely, during the LIA (1288–1606 ad ), cooling temperatures and frequent conflicts triggered significant migrations, particularly to the northern slopes, (i.e., during the Yuan‐Ming period) where conditions were more favorable. The center of gravity of the population relocated to the northern slopes of the Tian Shan Mountains. This shift promoted agricultural advancements in later periods, despite the challenges posed by the harsher climate.

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

Effect of curvature and taper on the hydrodynamic properties of seal whisker inspired cylinders in uniform flow and wake - Yuanji Yao; Qiao Hu; Long Tang; Tongqiang Fu; Liuhao Shan; Tengyue Li (Ocean Engineering, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Qualitatively elucidating the molecular characteristics of precursors for saturated halogenated disinfection byproducts in chlorinated urban eutrophic lake water by ultrahigh-resolution mass spectrometry - Shixi Wu; Qing-Long Fu; Manabu Fujii; Jibao Liu; Ahmed Elreedy; Xin Yang; Pingqing Fu; Yanxin Wang (Journal of Hazardous Materials, 2025)

Comprehensive evaluation of surface water in the Qujiang River Basin through a newly proposed water quality index combined with positive matrix factorization and hazard quotient/index model - Dong Fu; Xinruo Wang; Yanchuan Gong; Hua Liu; Ting Long; Lvshan Zhou; Chuntan Chen; Hanyi Liu (Journal of Environmental Chemical Engineering, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

The application of multi-arc volumetric modulated arc therapy and fixed-field intensity modulated radiotherapy in the treatment of gynecologic cancer with large planning target volume - Jia-Ling Song; Yi-Zhao Zhang; Zhi-Long Zhang; Zheng-Feng Fu; Peng-Fei Sun (Physical and Engineering Sciences in Medicine, 2025)

Branch segmentation and phenotype extraction of apple trees based on improved Laplace algorithm - Long Li; Wei Fu; Bin Zhang; Yuqi Yang; Yun Ge; Congju Shen (Computers and Electronics in Agriculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Chemodiversity of soil dissolved organic matter complementally improved by stepwise elution and electrospray ionization modes - Shasha Zhuo; Rong Qin; Qing-Long Fu (Organic Geochemistry, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

Sustainable ammonia leaching for efficient nickel and cobalt recovery from mixed hydroxide precipitate - Yu Wang; Yanjuan Zhang; Caixia Lv; Guangye Wei; Long Meng; Jiajie Fu; Zhihui Yu; Jingkui Qu (Journal of Environmental Chemical Engineering, 2025)

3D hierarchical porous hydrogel polymer electrolytes for flexible quasi-solid-state supercapacitors - Haoran Wang; Zhaoxia Hou; Yue Wang; Haibo Long; Depeng Zhang; Zhongchao Fu; Nan Wu; Zihui Zhai; Bo Wang (Chemical Engineering Journal, 2025)

Efficient bioleaching of Li from waste lithium–iron phosphate batteries by acidophilic bacterial consortium: Enrichment condition, Li recovery, and brief carbon footprint analysis - Jinghan Gu; Yuanyuan Nie; Zaiyu Li; Kun Yang; Long An; Haiqiang Jiang; Xiaoyu Han; Zhongtian Fu; Xin Zhao (Chemical Engineering Journal, 2025)

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

The evolution of sulfur during coalification in marine land interaction environments based on the sequential extraction of different sulfur species - Shuangxue Du; En Long; Yu Qi; Yiwen Ju; Pan Wu; Yong Fu; Shangyi Gu; Hao Zhang; Qingguang Li (Marine and Petroleum Geology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Insights into the seasonal characteristics of single particle aerosols in Chengdu based on SPAMS - Junke Zhang; Yunfei Su; Chunying Chen; Xinyi Fu; Yuhan Long; Xiaoxue Peng; Xiaojuan Huang; Gehui Wang; Wei Zhang (Journal of Environmental Sciences, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Social conditions alter the growth, metabolic rate, behavioral traits, and food-shelter preferences in the juvenile qingbo Spinibarbus sinensis - Yu-Lin Zhang; Wen-Qian Zhou; Shi-Jian Fu; Lauren E. Nadler; Shaun S. Killen; Ke-Ying Zhou; Shi-Long Zheng; Cheng Fu (Behavioral Ecology and Sociobiology, 2025)

Establishment and application of TaqMan probe-based quantitative real-time PCR for rapid detection and quantification of Ichthyophthirius multifiliis in farming environments and fish tissues - Shu-Quan Guo; Yao-Wu Fu; Ting-Long Hou; Shi-Lu Huang; Qi-Zhong Zhang (Veterinary Parasitology, 2025)

Dynamic analysis of intrahepatic T cells reveals a unique group of restorative Cxcr3+ tissue-resident CD4 T cells in acute liver injury - Shen-Xi Ouyang; Yong-Gang Xu; Peng Ding; Yue Long; Zhen Zhang; Si-Jia Sun; Yan Zhang; Hang Yin; Jia-Bao Zhang; Qi Cao; Fu-Ming Shen; Pei Wang; et al. (Toxicology, 2025)

Petrogenesis of the > 2.90 Ga komatiite in the Sujiagou region of the North China Craton: Implications for Archean mantle source and geodynamic setting - Rui Zuo; Xiaoping Long; Bin Wu; Mei-Fu Zhou (Precambrian Research, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Impact of oil phase volume fraction on the characteristics of w/o/w emulsions stabilized with alkali-heat-treated rice residue glutelin - Zhixiao Wang; Yuanbo Guo; Xiangjin Fu; Jianan Zhang; Qinlu Lin; Zhao Long; Weidan Guo (Food Research International, 2025)

Process and mechanism of 2,3-dichlorophenol reduction by microscale zero-valent iron-coupled Desulfitobacterium hafniense DCB-2 - Yue Lu; Jiahui Lei; Haoran Dong; Linrui Zhong; Qiqi Fu; Qingqing Xie; Long Li; Fangyi Liang (Chemical Engineering Journal, 2025)

Rigid interface induced structural transformation in Zn, Ni-ZIF for enhanced electromagnetic wave attenuation - Xueting Zhang; Shaocong Zhong; Pianpian Zhang; Anqi Lun; Baoshan Li; Junjie Fu; Xinyu Wang; Ya’nan Yang; Long Xia (Chemical Engineering Journal, 2025)

Mechanisms of hydraulic erosion control in different microrelief patterns of loess sloped farmland under continuous rainfall - Xinkai Zhao; Xiaoyu Song; Danyang Wang; Lanjun Li; Pengfei Meng; Chong Fu; Long Wang; Wanyin Wei; Yu Liu; Huaiyou Li (CATENA, 2025)

Hot syngas cleanup for pilot two-stage fluidized bed steam-oxygen biomass gasification plant - Zhijie Fu; Nazanin Charchi Aghdam; Sahand Nekoeian; Jing He; Long Cheng; Shida Liu; Lei Zhang; Junnan Chao; Xiaoyang Wei; Ruixu Wang; Bhavya Nagda; Yumeng Zhang; et al. (Bioresource Technology, 2025)

The Inversion of Seepage Parameters by Tidal and Barometric Response Methods: A Case Study of Shizhu Well with the Thick Aquifer Mixed with Mudstones - Qiuye Yang; Yan Zhang; Junliu Suwen; Xiao-long Sun; Tianming Huang; Junhua Hu; Shengwen Qi; Li-Yun Fu (Pure and Applied Geophysics, 2025)

Chemodiversity of coastal seawater dissolved organic matter shaped by wastewater treatment plant effluent in Tokyo Bay, Japan - Yanhui Cheng; Jibao Liu; Manabu Fujii; Qing-Long Fu (Applied Geochemistry, 2025)

Whole-genome re-sequencing reveals genetic structure and selection signals of different populations in Megalobrama amblycephala - Shi-Long Wang; Li-Fei Luo; Yue Yu; Yu-Ye Fu; Ze-Xia Gao (Aquaculture, 2025)

Enhancing the applicability of sisal fibers in cement-based materials through alkali treatment and penetrating crystallization - Juhong Liang; Xianfeng Wang; Zhipeng Fu; Zhangjian Li; Limin Liang; Qiling Luo; Wujian Long (Journal of Cleaner Production, 2025)

Study on decarbonizing ocean shipping propulsion power by liquid ammonia with centralized jet-flame controlled combustion strategy - Long Liu; Shiyi Fu (Journal of Cleaner Production, 2025)

Multiscale revelation of asphalt morphology and adhesion performance evolution during stress relaxation process - Fu Xu; Jing Deng; Yizhou Liu; Huijun Xie; Zhengwu Long; Botao Dai; Hao Yang; Lingyun You; Chongzheng Zhu; Dongzhao Jin (Fuel, 2025)

Effects of slurry ice treatment on the physicochemical changes and proteome of large yellow croaker (Larimichthys crocea) - Yan-wei Yuan; Yu-ting Liu; Xing-tong Zhu; Jin-xiu Yu; Jun-long Mao; Jing-jing Fu; Yue-wen Chen; Guo-feng Tan (Food Chemistry, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Optimizing soil resistance and disturbance of bionic furrow opener for paddy field based on badger claw using the CFD-DEM method - Zhenyu Tang; Zhiwei Zeng; Shuanglong Wu; Dengbin Fu; Jihan He; Yinghu Cai; Ying Chen; Hao Gong; Long Qi (Computers and Electronics in Agriculture, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

PBAT biodegradable microplastics enhanced organic matter decomposition capacity and CO2 emission in soils with and without straw residue - Sha Chang; Chao Chen; Qing-Long Fu; Aoyu Zhou; Zhuyao Hua; Fengxiao Zhu; Shiyin Li; Huan He (Journal of Hazardous Materials, 2024)

Hierarchical evolutionary modeling and performance multi-objective optimization of centrifugal air compressors for fuel cells under multi-operating conditions - Xilei Sun; Guanjie Zhang; Tingpu He; Jianqin Fu; Wuqiang Long (Journal of Cleaner Production, 2024)

Synthesis of CoFe2O4@C based on Fe/Co-BTC for efficient detection, determination and degradation of nitenpyram residue: An electrochemical study, condition optimization and mechanism - Yuan-Zhen Wang; Guo-Qiang Xu; Yu-Han Sun; Liu Yang; Yu-Long Liu; Ying Fu (Journal of Cleaner Production, 2024)

Effects of iron oxide minerals on the pyrolysis of polyvinyl chloride: Catalytic dechlorination, chlorine capture, and carbon sequestration - Ziyi Ding; Runliang Zhu; Qingru Xie; Shiqin Long; Haoyang Fu; Qingze Chen; Yunfei Xi (Journal of Cleaner Production, 2024)

Improving rice quality through biochar application in China: A meta–analysis - Hui He; Li Long; Zhiqiang Fu (Journal of Environmental Management, 2024)

Detecting and attributing the impact of human activities on grassland aboveground biomass in China's Loess Plateau - Jian-Zhou Wei; Jiu-Ying Pei; Chao Fang; Jordi Sardans; Josep Peñuelas; Fu-Qiang Huang; Xu-Long Zhang; Kai Zheng (Journal of Environmental Management, 2024)

Bifunctional reduced graphene oxide/polyelectrolytes/MoS2-AuNPs hybrids with Vis/NIR photocatalytic and photothermal activities for biosafe and efficient antibacterial applications - Meng Fu; Chang Luo; Qi Yuan; Zequn Ma; Quansheng Long; Baihui Liu; Dang Wu; Jingshui Xu; Xiangming Li (Journal of Environmental Chemical Engineering, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Revealing the key antioxidant compounds and potential action mechanisms of Chinese Cabernet Sauvignon red wines by integrating UHPLC-QTOF-MS-based untargeted metabolomics, network pharmacology and molecular docking approaches - Zhi-Xin Peng; Hui-Wen Gu; Yuan Pan; Yan Wang; Jun Yan; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Self-healing, photoluminescent elastomers for 3D printing fabrication of flexible sensors - Chunyi Luo; Xin Luo; Danyang Liu; Guangmeng Ma; Longfei Zhang; Jianglin Fu; Yu Li; Fawei Guo; Mingtao Zhang; Yu Long (Chemical Engineering Journal, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Dual-channel fluorescent probe for detecting SO2 and Hg2+, and dynamic imaging SO2 under Cd2+ in alfalfa (Medicago sativa) - Ya-Qian Wu; Xiang-Yu Wang; Tian-Wen Bai; Ying-Long Fu (Analytica Chimica Acta, 2024)

Vision-based trajectory generation and tracking algorithm for maneuvering of a paddy field robot - Dengbin Fu; Zhiying Chen; Zhiqiang Yao; Zhanpeng Liang; Yinghu Cai; Chuang Liu; Zhenyu Tang; Caixia Lin; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2024)

The development of novel genome-SSRs, multiplex PCR panels, and allelic ladders for parentage identification in Tachypleus tridentatus - Boyu Chen; Ju Long; Jinxia Liu; Pengliang Wang; Zihang Ma; Zhenyu Lan; Ziwei Liang; Qianni Fu; Zining Zhang; Yan Zhang; Yitao Duan; Peng Zhu; et al. (Aquaculture, 2024)

Mechanisms of N-doped microporous biochar decreased Cd transition in rhizosphere soils and its impact on soil bacterial community composition - Honghong Li; Zhou Li; Jun Long; Jiayi Fu; Chen Chen (Science of The Total Environment, 2024)

Load-bearing characteristics of surface conductor in deepwater gas hydrate formations - Chao Fu; Jin Yang; Zhangxing John Chen; Qishuai Yin; Yang Long; Lei Li; Abimbola Fatai Akorede (Ocean Engineering, 2024)

Distribution, sources, impact factors and ecological risks of sediment heavy metals from typical estuarine wetlands in tropical islands - Kaizhe Fu; Zeheng Chen; Cheng Huang; Yuanyuan Chen; Dongming Wu; Xiwen Li; Yanwei Song; Weipin Ding; Xiujiu Yang; Junqiao Long (Estuarine, Coastal and Shelf Science, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Zinc oxide nanoparticles and nano-hydroxyapatite enhanced Cd immobilization, activated antioxidant activity, improved wheat growth, and minimized dietary health risks in soil-wheat system - Guangxin Li; Ran Duan; Xinran Liang; Hongen Liu; Shiyu Qin; Long Wang; Haichao Fu; Peng Zhao; Chang Li (Journal of Environmental Chemical Engineering, 2024)

Fraction-dependent variations in cooling efficiency of urban trees across global cities - Wenfeng Zhan; Chunli Wang; Shasha Wang; Long Li; Yingying Ji; Huilin Du; Fan Huang; Sida Jiang; Zihan Liu; Huyan Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A novel “on-off-on” electrochemiluminescence aptasensor based on resonance energy transfer as signal amplification strategy for ultrasensitive detection of sulfadiazine in different samples - Youqi Long; Junjie Liu; Yijie Wu; Lin Fu; Lijuan Bai (Food Chemistry, 2024)

Integration of CaO2/Fe2+ and ultrafiltration acts as multiple-workfunctions pretreatment for seawater desalination during harmful algal blooms - Boyan Xu; Yuyao Fu; Xiaohui Lu; Zihao Li; Meibo He; Wee Joon Teo; Weilong Song; Long D. Nghiem; Sungwoo Bae; How Yong Ng (Desalination, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

China’s urban green growth from 2000 to 2020 is influenced by legacy effects - Hai-Li Zhang; Hao Xiu; Mir Muhammad Nizamani; Qing Zhou; Kaijun Long; Yunfan Quan; Tingting Fu; Qinghui Sun (Urban Ecosystems, 2024)

In-situ remediation of cadmium contamination in paddy fields: from rhizosphere soil to rice kernel - Hai Yan Long; Guang Fu Feng; Jun Fang (Environmental Geochemistry and Health, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Deep-sea implosion of spherical pressure shell considering geometric imperfection - Fu-Jin Yang; Yun-Long Liu; Jun Wang; Bao-Jian Wang; Jun Guo (Ocean Engineering, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Norfloxacin affects inorganic nitrogen compound transformation in tailwater containing Corbicula fluminea - Junling Wei; Zijin Hong; Wei Li; Xiufang Yang; Zihao Fu; Xinyu Chen; Junxiang Hu; Zhangnan Jin; Bojiang Long; Xuexiu Chang; Yu Qian (Journal of Hazardous Materials, 2024)

Versatile applications and mechanisms of genus Exiguobacterium in bioremediating heavy metals and organic pollutants: A review - Min Xiao; Zhong-er Long; Xueqin Fu; Long Zou (International Biodeterioration & Biodegradation, 2024)

A colorimetric sensor based on 4-MPBA Au@AgNPs for accurately identification of EnshiYulu tea grade - Yuting Guan; Siyu Wang; Guanghua Lei; Zikang Hu; Hengye Chen; Huiwen Gu; Xiaoli Yin; Yuanbin She; Wanjun Long; Haiyan Fu (Food Chemistry, 2024)

Application of various polysaccharide gums to improve gelation and rheological properties of hydroxypropyl starch hydrocolloids - Jun Fu; Xingzhe Cai; Yiwen Yang; Huifang Xie; Qingfei Duan; Hongsheng Liu; Long Yu (Food Hydrocolloids, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Bioinspired carbon black deposited polyimide fabric for sustainable water energy harvesting - Jianhong Guo; Leyan Zhang; Chunhua Zhang; Dandan Zhong; Weihao Long; Jieyao Qin; Zhuan Fu; Sijie Zhou; Junyao Gong; Heng Pan; Hua Ji; Lixin Du; et al. (Chemical Engineering Journal, 2024)

Asymmetrical changes of electron-donating and electron-accepting capacities of natural organic matter during its interaction with Fe oxyhydroxides - Yiran Liu; Weijun Zhao; Peng Zhang; Qing-long Fu; Chenglong Yu; Songhu Yuan (Chemical Geology, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

Effects of three different protein levels on the growth, gonad development, and physiological biochemistry of female Pengze crucian carp (Carassius auratus var. Pengze) broodstock - Jun Xiao; Fan Long; Liyun Ding; Yuan Yao; Weihua Wu; Yilong Fu; Wenjing Chen (Frontiers in Marine Science, 2024)
A 56-days feeding experiment was conducted to evaluate the effect of dietary protein levels on fish growth, gonad development, and physiological biochemistry of female Pengze crucian carp ( Carassius auratus var. Pengze) broodstock. Three isoenergetic diets were formulated, and the crude protein levels were 26.85%, 35.73% and 44.38%, the lipid levels were 7.39%, 7.92% and 7.91%, respectively. The results showed that the weight gain rate (WGR), the specific growth rate (SGR) and the protein efficiency ratio (PER) of the female Pengze crucian carp broodstock increased significantly and the feed conversion ratio (FCR) decreased significantly when the dietary protein level was 35.73% ( P < 0.05). The WGR, the SGR and the PER were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). Increasing dietary protein levels led to a significant increase in the gonad index and the egg menstrual length of the female Pengze crucian carp broodstock ( P <0.05). The higher protein levels resulted in a significant increase in total amino acids, total essential amino acids, and total nonessential amino acids ( P <0.05). The varying ovaries of each group of total saturated fatty acids, total highly unsaturated fatty acids, and total polyunsaturated fatty acids all increased significantly with increasing protein levels ( P <0.05). Furthermore, the aspartate transaminase (AST), low-density lipoprotein cholesterol (LDLC), and malondialdehyde (MDA) contents in plasma were significantly lower in the 35.73% and 44.38% groups than in the 26.85% group ( P < 0.05). The 35.73% group exhibited the highest plasma superoxide dismutase (SOD) activity,. The plasma vitellogenin (VTG), estradiol 2 (E2), and progesterone (PROG) in plasma of female Pengze crucian carp broodstock were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). The results showed that the addition of an appropriate amount of protein to the feed can significantly improve the growth, gonadal development, and health of female Pengze crucian carp. In this study, the effect of 35.73% protein concentration was better than in the other two groups.

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Social Learning with Actor–Critic for dynamic grasping of underwater robots via digital twins - Xubo Yang; Jian Gao; Peng Wang; Wenyi Long; Chongbo Fu (Ocean Engineering, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Effects of shading & calcium peroxide suspension on landscape water quality and CH4 and N2O production - Tian-Tian Fu; Yi Wang; Hui-Ying Zhao; Zhen-Hao Liang; Kai Zhang; Yue-Ning Wang; Hui-Long Ouyang; Jia-Ni Yin; Yong-Qiang Liu (Journal of Water Process Engineering, 2024)

Discrimination and prediction of Qingzhuan tea storage year using quantitative chemical profile combined with multivariate analysis: Advantages of MRMHR based targeted quantification metabolomics - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Molecular mechanism of a coastal cyanobacterium Synechococcus sp. PCC 7002 adapting to changing phosphate concentrations - Qiao-Wei Sun; Yu Gao; Jordan Wang; Fei-xue Fu; Cheng-Wen Yong; Shuang-Qing Li; Hai-Long Huang; Wei-Zhong Chen; Xin-Wei Wang; Hai-Bo Jiang (Marine Life Science & Technology, 2024)
Phosphorus concentration on the surface of seawater varies greatly with different environments, especially in coastal. The molecular mechanism by which cyanobacteria adapt to fluctuating phosphorus bioavailability is still unclear. In this study, transcriptomes and gene knockouts were used to investigate the adaptive molecular mechanism of a model coastal cyanobacterium Synechococcus sp. PCC 7002 during periods of phosphorus starvation and phosphorus recovery (adding sufficient phosphorus after phosphorus starvation). The findings indicated that phosphorus deficiency affected the photosynthesis, ribosome synthesis, and bacterial motility pathways, which recommenced after phosphorus was resupplied. Even more, most of the metabolic pathways of cyanobacteria were enhanced after phosphorus recovery compared to the control which was kept in continuous phosphorus replete conditions. Based on transcriptome, 54 genes potentially related to phosphorus-deficiency adaptation were selected and knocked out individually or in combination. It was found that five mutants showed weak growth phenotype under phosphorus deficiency, indicating the importance of the genes ( A0076 , A0549-50 , A1094 , A1320 , A1895 ) in the adaptation of phosphorus deficiency. Three mutants were found to grow better than the wild type under phosphorus deficiency, suggesting that the products of these genes ( A0079 , A0340 , A2284–86 ) might influence the adaptation to phosphorus deficiency. Bioinformatics analysis revealed that cyanobacteria exposed to highly fluctuating phosphorus concentrations have more sophisticated phosphorus acquisition strategies. These results elucidated that Synechococcus sp. PCC 7002 have variable phosphorus response mechanisms to adapt to fluctuating phosphorus concentration, providing a novel perspective of how cyanobacteria may respond to the complex and dynamic environments.

Disturbance intensity shapes the soil micro-food web compositions and energy fluxes during seven-year land use changes - Xianwen Long; Jie Zhao; Jiangnan Li; Xionghui Liao; Jiachen Wang; Zhiyong Fu; Wei Zhang; Xiajiao Liu; Kelin Wang (Soil Biology and Biochemistry, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Colorimetric aptasensor utilizing MOF-235 with exceptional peroxidase-like activity for the detection of oxytetracycline residues in raw milk - Long Wang; Xia Lu; Yan Zhang; Yuxin Wang; Yi Ding; Mengjia Liu; Shangchen Fu; Wupeng Ge (Food Chemistry, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

Electronic-rich large conjugated molecules dispersing through ionic liquid solution process for fluorescent detection of iodine gas - Yue-Ru Zhou; Shuang-Long Wang; Lei Zhang; Jie Fu; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2024)

In vitro and in vivo activity of ceftazidime/avibactam and aztreonam alone or in combination against mcr-9, serine- and metallo-β-lactamases–co-producing carbapenem-resistant Enterobacter cloacae complex - Wengang Li; Jisheng Zhang; Yanjun Fu; Jianmin Wang; Longjin Liu; Wenzhang Long; Kaixin Yu; Xinhui Li; Chunli Wei; Xushan Liang; Jin Wang; Chunjiang Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Physics-based seismic analysis of ancient wood structure: fault-to-structure simulation - Zhenning Ba; Jisai Fu; Fangbo Wang; Jianwen Liang; Bin Zhang; Long Zhang (Earthquake Engineering and Engineering Vibration, 2024)

RETRACTED: Effect of calcium and phosphorus on ammonium and nitrate nitrogen adsorption onto iron (hydr)oxides surfaces: CD-MUSIC model and DFT computation - Mengke Jia; Jie Ma; Qiongqiong Zhou; Lijie Liu; Xiaolei Jie; Hongen Liu; Shiyu Qin; Chang Li; Fuqing Sui; Haichao Fu; Haijiao Xie; Long Wang; et al. (Chemosphere, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

When antibiotics encounter microplastics in aquatic environments: Interaction, combined toxicity, and risk assessments - Yibo Zhang; Xin Xu; Jing Xu; Zhang Li; Long Cheng; Jie Fu; Weiling Sun; Chenyuan Dang (Science of The Total Environment, 2024)

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

Improving water quality and mitigating CH4 and N2O production in urban landscape water simultaneously by optimizing calcium peroxide dosage - Zhen-Hao Liang; Yi Wang; Hui-Ying Zhao; Tian-Tian Fu; Yong-Qiang Liu; Kai Zhang; Yue-Ning Wang; Hui-Long Ouyang; Jia-Ni Yin (Science of The Total Environment, 2024)

Elevated nitrogen loadings facilitate carbon dioxide emissions from urban inland waters - Yong-Mei Hou; Fu-Jun Yue; Si-Liang Li; Xiao-Long Liu (Journal of Environmental Management, 2024)

Response of ocean acidification to atmospheric carbon dioxide removal - Jiu Jiang; Long Cao; Xiaoyu Jin; Zechen Yu; Han Zhang; Jianjie Fu; Guibin Jiang (Journal of Environmental Sciences, 2024)

Dual-role KCl-assisted fabrication of porous carbon with controllable architecture from coal liquefaction residue for supercapacitors - Xiaoxia Yang; Guoxiao Sun; Fei Wang; Long Chen; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Feng Fu; Ru’an Chi (Fuel, 2024)

Correlations of dynamic changes in lipid and protein of salted large yellow croaker during storage - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Research International, 2024)

Three-dimensional fluorescence combined with alternating trilinear decomposition and random forest algorithm for the rapid prediction of species, geographical origin and main components of Glycyrrhizae Radix et Rhizoma (Gancao) - Hengye Chen; Lixue Ren; Yinan Yang; Wanjun Long; Wei Lan; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

Nutritional- and flavor-enhancing effects of biomass production by Rhodotorula spp. on cantaloupe juice - Ruitong Hou; Shuyu Liu; Na Lv; Baozhong Cui; Yongxue Wei; Feiyang Long; Hongfei Fu; Yunyang Wang (Food Bioscience, 2024)

Joint inversion of full-tensor gravity gradiometry data based on source growing - Zhen-Long Hou; Xin-Yang Zhao; Dai-Lei Zhang; Fu-Quan Zhao; Jia-Hui Wang (Applied Geophysics, 2024)

Law of respirable dust pollution induced by cutting-advancing support in a fully mechanized mining face and spatial stereoscopic dust control and removal technology - Shuzheng Song; Gang Zhou; Biao Sun; Genru Zhou; Honglei Wei; Yunna Wang; Zhenkun Fu; Zhen Liu; Long Meng (Environment, Development and Sustainability, 2024)

Nitrogen migration and transformation during re-suspension and photo-induction in landscape water replenished by reclaimed water - Hui-Ying Zhao; Zhen-Hao Liang; Kai Zhang; Jia-Ni Yin; Tian-Tian Fu; Yue-Ning Wang; Hui-Long OuYang; Yi Wang (Environmental Science and Pollution Research, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Elucidation of the dominant factors influencing N2O emission in water-level fluctuation zones in a karst canyon reservoir, southwest China - Sai-Nan Chen; Yongmei Hou; Fu-Jun Yue; Zhifeng Yan; Xiao-Long Liu; Si-Liang Li (Science of The Total Environment, 2024)

Exposure to heavy metallic and trace essential elements and risk of diminished ovarian reserve in reproductive age women: A case-control study - Tian Tian; Zheng Wang; Fang Liu; Yu Fu; Fei Kong; Yuanyuan Wang; Qin Li; Xiaoyu Long; Jie Qiao (Journal of Hazardous Materials, 2024)

Nano effect fluorescence visual sensor based on Au-AgNCs: A novel strategy to identify the origin and growth year of Lilium bulbs - Siyu Wang; Wanjun Long; Liuna Wei; Wenyu Cheng; Hengye Chen; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Efficient detection of flusilazole by an electrochemical sensor derived from MOF MIL-53(Fe) for food safety - Yu-Han Sun; Liu Yang; Xian-Xian Ji; Yuan-Zhen Wang; Yu-Long Liu; Ying Fu; Fei Ye (Food Chemistry, 2024)

Biocompatible porous material templated from gliadin particle and gellan gum co-stabilized wet foam - Fu-Zhen Zhou; Tao Yang; Huan Xiang; Long-Tao Zhang; Shu-Heng Wei; Jian-Hua Zhu; Xiao-Quan Yang; Shou-Wei Yin (Food Hydrocolloids, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Unraveling hierarchical hollow NiCo2S4/MXene/N-doped carbon microspheres via dual templates for high-performance hybrid supercapacitors - Baobao Li; Lu Zhang; Zhibo Zhao; Yuxi Zou; Bingqi Chen; Xiaoguang Fu; Fangqiao Wang; Sishi Long; Wenxi Guo; Jinxia Liang; Meidan Ye (Chemical Engineering Journal, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Late Cenozoic uplift of the Liupan Mountains: Evidence from the Neogene loess deposits - Zhilin He; Yansong Qiao; Zhengtang Guo; Chaoqin Chen; Long Chen; Yang Fu; Ye Yang; Yanxia Liang; Xinru Lin; Guoqiao Xiao; Tao Zhan (Science China Earth Sciences, 2024)

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

Deep leaning in food safety and authenticity detection: An integrative review and future prospects - Yan Wang; Hui-Wen Gu; Xiao-Li Yin; Tao Geng; Wanjun Long; Haiyan Fu; Yuanbin She (Trends in Food Science & Technology, 2024)

MAPK/NF-κB signaling mediates atrazine-induced cardiorenal syndrome and antagonism of lycopene - Fu-Wei Jiang; Jian-Ying Guo; Jia Lin; Shi-Yong Zhu; Xue-Yan Dai; Muhammad Asmat Ullah Saleem; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

Curation, nomenclature, and topological classification of receptor-like kinases from 528 plant species for novel domain discovery and functional inference - Qian Liu; Qiong Fu; Yujie Yan; Qian Jiang; Longfei Mao; Long Wang; Feng Yu; Heping Zheng (Molecular Plant, 2024)

External electricity-powered FeS/graphene/bacterial hybrid for Cr6+ removal from water lacking organic electron donors - Qi Zhu; Fei Feng; Zhong-er Long; Yunhong Huang; Haiyan Ni; Xueqin Fu; Longhai Dai; Long Zou (Journal of Environmental Chemical Engineering, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

Authenticity identification of high – Temperature Daqu Baijiu through multi-channel visual array sensor of organic dyes combined with smart phone App - Yanmei Zhu; Fushuang Xiang; Yuanyuan Su; Xue Jiang; Yipeng Cang; Wanjun Long; Wei Lan; Gaoqiong Deng; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

Hybrid LBM and machine learning algorithms for permeability prediction of porous media: A comparative study - Qing Kang; Kai-Qi Li; Jin-Long Fu; Yong Liu (Computers and Geotechnics, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Chemical composition, sources, and processes of winter haze in Chengdu, China: Insights from integrating the bulk chemical and single particle approaches - Junke Zhang; Wei Sun; Yunfei Su; Xiaoxue Peng; Chunying Chen; Xinyi Fu; Yuhan Long; Gehui Wang; Zhihan Rao; Lin Han; Xiaojuan Huang (Atmospheric Environment, 2024)

Baseline sensitivity and fungicidal action of iminoctadine tris (albesilate) against Geotrichum citri-aurantii - Kunyu Zhang; Yanping Fu; Chaoan Long; Fuxing Zhu (European Journal of Plant Pathology, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Hierarchically porous magnetic biochar as an amendment for wheat (Triticum aestivum L.) cultivation in alkaline Cd-contaminated soils: Impacts on plant growth, soil properties and microbiota - Haichao Fu; Shuanglong Ma; Long Wang; Weijie Xue; Shiwu Xiong; Fuqing Sui; Hongen Liu; Chang Li; Guangxin Li; Ran Duan; Peng Zhao (Chemosphere, 2024)

Synthesizing cationic polymers and tuning their properties for microalgae harvesting - Lisa Aditya; Hang P. Vu; Md Abu Hasan Johir; Shudi Mao; Ashley Ansari; Qiang Fu; Long D. Nghiem (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Bio-based ionic liquid filter with enhanced electrostatic attraction for outside filtration and inside collection of viral aerosols - Guo-Hao Zhang; Qiu-Hong Zhu; Lei Zhang; Lei Li; Jie Fu; Shuang-Long Wang; Wen-Li Yuan; Ling He; Guo-Hong Tao (Journal of Hazardous Materials, 2024)

Selective enrichment of virulence factor genes in the plastisphere under antibiotic and heavy metal pressures - Lu Wang; Tian-Lun Zhang; Qian Xiang; Chen-Xi Fu; Min Qiao; Long-Jun Ding; Dong Zhu (Journal of Hazardous Materials, 2024)

Synthesis of one-part geopolymers from alkaline-activated molybdenum tailings: Mechanical properties and microstructural evolution - Youzhi Yang; Jinrui Zhang; Yin Fu; Wujian Long; Biqin Dong (Journal of Cleaner Production, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Effects of dimethyl ether blending on H2-fueled combustion characteristics and thermal improvement in fuel-lean condition - Jia Wei; Hao Wang; Qingguo Peng; Xinghua Tian; Feng Yan; Long Zhang; Peng Teng; Shuai Fu (Fuel, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Highly efficient solution-processable four-coordinate boron compound: A thermally activated delayed fluorescence emitter with short-lived phosphorescence for OLEDs with small efficiency roll-off - Zhengqin Pan; Jie Pan; Long Sang; Zhenming Ding; Meihua Liu; Laichao Fu; Mengqiu Wang; Xiaokang Huang; Bowen Li; Shaofeng Chen; Dongcheng Chen; Yu Liu; et al. (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Identification and characterization of β3 integrin in Crassostrea hongkongensis - Lei Tang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Thermal degradation kinetics of cynatratoside-C and its antiparasitic efficacy after being stored in sterile water and aquaculture water - Shi-Lu Huang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Homoerythrina-type alkaloids with neuroprotective activity from the branches of Cephalotaxus hainanensis Li - Hao Yan; Hao Wang; Peng-Wei Chen; Li Yang; Hui-Qin Chen; Fei Wu; Pei Wang; Hao-Fu Dai; Xiao-Long Huang; Shuang-Qing Zhou; Wen-Li Mei (Phytochemistry Letters, 2024)

Fish gelatin and gellan gum mixture as edible ink for 3D printing - Ming-hao Bian; Song-ying Jiang; Shi-long Liu; Long-tao Zhang; Song Miao; Fu-zhen Zhou; Bao-dong Zheng (Journal of Food Engineering, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

Iminoctadine tris (albesilate) resistance in Geotrichum citri-aurantii and its management - Kunyu Zhang; Yanping Fu; Chaoan Long; Fuxing Zhu (Crop Protection, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Study on the lateral thermal disturbances of three parallel embankments on permafrost along the Gonghe-Yushu Engineering Corridor in China - Binhua Hu; Long Jin; Yanhui Niu; Zhipeng Fu; Xu Li; Yuanhong Dong; Kun Yuan; Ziqiao Zhao (Transportation Geotechnics, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Characterization of summertime single aerosol particles in Chengdu (China): Interannual evolution and impact of COVID-19 lockdown - Junke Zhang; Chunying Chen; Yunfei Su; Wenkai Guo; Xinyi Fu; Yuhan Long; Xiaoxue Peng; Wei Zhang; Xiaojuan Huang; Gehui Wang (Science of The Total Environment, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

Fluorescent and smartphone imaging detection of tetracycline residues based on luminescent europium ion-functionalized the regular octahedral UiO-66-NH2 - Xiaoyue Yue; Long Fu; Jingwen Zhou; Yan Li; Min Li; Yawen Wang; Yanhong Bai (Food Chemistry, 2024)

Online and in-situ monitoring of the growth of silver nanowires and nanoparticles with conductive measurement - Huangqing Ye; Xuchao Jian; Ying Wang; Jun Long; Xiaofang Zhang; Junqin Wu; Yingying Pan; Yu Wang; Xiping Zeng; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Investigating the reliability of estimating real-time air exchange rates in a building by using airborne particles, including PM1.0, PM2.5, and PM10: A case study in Suzhou, China - Nuodi Fu; Moon Keun Kim; Long Huang; Jiying Liu; Bing Chen; Stephen Sharples (Atmospheric Pollution Research, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Catalytic degradation of crystal violet and methyl orange in heterogeneous Fenton-like processes - Long Wang; Chunbao Zhou; Yanxin Yuan; Yajie Jin; Yang Liu; Zhihui Jiang; Xiangtong Li; Jianjun Dai; Yingwen Zhang; Asif Ali Siyal; Wenya Ao; Jie Fu; et al. (Chemosphere, 2023)

Buprofezin affects the molting process by regulating nuclear receptors SfHR3 and SfHR4 in Sogatella furcifera - Gui-Yun Long; Ming-Fu Gong; Hong Yang; Xi-Bin Yang; Cao Zhou; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2023)

A novel 3D-fluorescence sensing strategy based on HN-chitosan polymer probe for rapid identification and quantification of potential adulteration in saffron - Wanjun Long; Gaoqiong Deng; Yanmei Zhu; Qingyang Han; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Lipidomics reveals the relationship between lipid oxidation and flavor formation of basic amnio acids participated Low-Sodium cured large yellow croaker - Min Zhang; Jing-Jing Fu; Jun-Long Mao; Xiu-Ping Dong; Yue-Wen Chen (Food Chemistry, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Separated two-stage hydrothermal liquefaction of livestock manure for high-quality bio-oil with low-nitrogen content: Insights on nitrogen migration and evolution - Siyuan Long; Haiwei Jiang; Jinming Shi; Xianbin Ai; Zhigang Que; Hanbing Nie; Chunbao Charles Xu; Rong Huang; Yinxuan Fu; Weiran Yang (Chemical Engineering Journal, 2023)

Polyethylene microplastics cause apoptosis via the MiR-132/CAPN axis and inflammation in carp ovarian - Meng-ran Zhu; Hong-ru Wang; Fu-xin Han; Zhao-long Cai; Jing-jing Wang; Meng-yao Guo (Aquatic Toxicology, 2023)

IGF2 is upregulated by its antisense RNA to potentiate pancreatic cancer progression - Yuan Tian; Wenwen Han; Long Fu; Jing Zhang; Xinhua Zhou (Functional & Integrative Genomics, 2023)

Effects of simulated warming on soil properties and bacterial community composition in the Bashania faberi ecosystem - Jianchao Fu; Jun Wu; Min Xu; Jing Ma; Lulu Long; Chao Chen; Gang Yang; Chun Song; Xiaohong Zhang; Hongbo Yang; Jindong Zhang (Applied Soil Ecology, 2023)

Comparative analysis of the cardiac structure and transcriptome of scallop and snail, perspectives on heart chamber evolution - Meina Lu; Rabia Hayat; Xuejiao Zhang; Yaqi Jiao; Jianyun Huang; Yifan Huangfu; Mingcan Jiang; Jieyi Fu; Qingqiu Jiang; Yaojia Gu; Shi Wang; Alexander A. Akerberg; et al. (Marine Life Science & Technology, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Characterization of halogenated organic compounds by the Fourier transform ion cyclotron resonance mass spectrometry: A critical review - Shixi Wu; Manabu Fujii; Xin Yang; Qing-Long Fu (Water Research, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

Rapid identification of high-temperature Daqu Baijiu with the same aroma type through the excitation emission matrix fluorescence of maillard reaction products - Hengye Chen; Yanmei Zhu; Yufei Xie; Wanjun Long; Wei Lan; Yuanbin She; Haiyan Fu (Food Control, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Understanding how microbial electrolysis cell assisted anaerobic digestion enhances triclocarban dechlorination in sludge - Sha Long; Qizi Fu; Zhixiang Hao; Luyang Sun; Zihan Li; Yike Guo; Xuran Liu; Fengming Song; Dongbo Wang; Wenming Wang (Chemical Engineering Journal, 2023)

IrOx-MoO3 nano-heterostructure electrocatalysts for efficient acidic water oxidation - Yurong Chen; Danni Liu; Qianqian Zhao; Xin Long; Jie Wang; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2023)

Insights into the roles of DOM in humification during sludge composting: Comprehensive chemoinformatic analysis using FT-ICR mass spectrometry - Jibao Liu; Ning Wang; Manabu Fujii; Zhen Bao; Jinyi Wei; Zhineng Hao; Qing-long Fu; Rongjun Gao; Jingfu Liu; Yuansong Wei (Chemical Engineering Journal, 2023)

Performance analyses of two-phase closed thermosyphons for road embankments in the high-latitude permafrost regions - Guan-fu Wang; Chuang Lin; Long Zhu; De-cheng Feng; Yang-yang Xin; Feng Zhang (Journal of Mountain Science, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

Energy, Exergy and Environmental Analysis of ORC Waste Heat Recovery from Container Ship Exhaust Gases Based on Voyage Cycle - Long Lyu; Ankang Kan; Wu Chen; Yuan Zhang; Bingchun Fu (Journal of Marine Science and Engineering, 2023)
Recovering the waste heat of a marine main engine (M/E) to generate electricity was an environmental way to minimize the carbon dioxide emissions for ships, especially with organic Rankine cycle (ORC) technology. The M/E had variable loads and operating times during voyage cycle, which directly affected the ORC thermodynamic potential. In this paper, a voyage cycle-based waste heat utilization from the M/E was introduced to provide reliable evaluation for proposing and designing ORC. The effect of various M/E loads and operating times on ORC performance among three dry-type substances was analyzed. The environmental impact was presented based on the data from one voyage cycle navigation of objective container ship. The results showed that Cyclohexane was capable of net power while Benzene was more suitable for thermal efficiency. The evaporator and condenser were the main irreversible components of the ORC system and required further optimization. Taking the operational profile into consideration, the evaporation pressures were 922–1248 kPa (Cyclohexane), 932–1235 kPa (Benzene) and 592–769 kPa (Toluene), respectively. During the voyage cycle, the carbon dioxide emissions were 99.68 tons (Cyclohexane), 96.32 tons (Benzene) and 60.99 tons (Toluene), respectively. This study provided certain reference for the design and investigation of ORC application to further improve the energy efficiency for container ship.

Classification of Chinese traditional cereal vinegars and antioxidant property predication by fluorescence spectroscopy - Wanjun Long; Guanghua Lei; Yuting Guan; Hengye Chen; Zikang Hu; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Polydopamine-coated HKUST MOFs-based strip lateral flow immunoassay for on-site ultrasensitive detection of aflatoxin B1 in foods - Wenjuan Wu; Ying Li; Qingbin Xu; Nan Long; Pengyue Song; Jiabo Wang; Lidong Zhou; Bin Fu; Weijun Kong (Food Control, 2023)

Highly efficient C@Ni-Pd bifunctional electrocatalyst for energy-saving hydrogen evolution and value-added chemicals co-production from ethanol aqueous solution - Hao Chen; Xuexian Wu; Danni Liu; Chunyi Ye; Lingui Huang; Xin Long; Lei Wang; Jiujun Zhang; Jing-Li Luo; Xian-Zhu Fu (Chemical Engineering Journal, 2023)

Fibrous mats based skin sensor with ultra-sensitivity and anti-overshooting dynamic stability enhanced with artificial intelligence - Hui Chen; Jian Zhou; Xinxin Long; Fengling Zhuo; Ying Liu; Yihan Zhao; Jianfei Xie; Huigao Duan; Yongqing Fu (Chemical Engineering Journal, 2023)

Efficient 2-O-α-D-glucopyranosyl-sn-glycerol production by single whole-cell biotransformation through combined engineering and expression regulation with novel sucrose phosphorylase from Leuconostoc mesenteroides ATCC 8293 - Peifeng Duan; Mengfei Long; Xian Zhang; Zuyi Liu; Jiajia You; Xuewei Pan; Weilai Fu; Meijuan Xu; Taowei Yang; Minglong Shao; Zhiming Rao (Bioresource Technology, 2023)

Contributions of annual and semiannual tidal constituents to chart datum in the China seas and adjacent waters - Yikai Feng; Yanguang Fu; Long Yang; Dongxu Zhou (Acta Oceanologica Sinica, 2023)

Reducing carbon footprints and increasing net ecosystem economic benefits through dense planting with less nitrogen in double-cropping rice systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Kangyu Zhong; Rui Xiong; Feipeng Xie; Fugui Chen; Zhiqiang Fu (Science of The Total Environment, 2023)

Divergent urbanization-induced impacts on global surface urban heat island trends since 1980s - Long Li; Wenfeng Zhan; Leiqiu Hu; TC Chakraborty; Zhihua Wang; Peng Fu; Dazhong Wang; Weilin Liao; Fan Huang; Huyan Fu; Jiufeng Li; Zihan Liu; et al. (Remote Sensing of Environment, 2023)

A sensitized ratiometric fluorescence probe based on N/S doped carbon dots and mercaptoacetic acid capped CdTe quantum dots for the highly selective detection of multiple tetracycline antibiotics in food - Yao Fan; Lu Shen; Yaqi Liu; Ying Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

A top-down deep learning model for predicting spatiotemporal dynamics of groundwater recharge - Xin Huang; Lei Gao; Nan Zhang; Russell S. Crosbie; Long Ye; Jian Liu; Zhaoxia Guo; Qinghua Meng; Guobin Fu; Brett A. Bryan (Environmental Modelling & Software, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Seasonal variations in precipitation microphysics over East China based on GPM DPR observations - Long Wen; Gang Chen; Cha Yang; Hao Zhang; Zhaoyang Fu (Atmospheric Research, 2023)

Spatial-temporal patterns and influencing factors for pulmonary tuberculosis transmission in China: an analysis based on 15 years of surveillance data - Xiao Wei; Ting Fu; Di Chen; Wenping Gong; Shuyuan Zhang; Yong Long; Xubin Wu; Zhongjun Shao; Kun Liu (Environmental Science and Pollution Research, 2023)

An advanced treatment process for 3-high wastewater discharged from crude oil storage tanks - Xue-Wen Li; Zhong-Yi Cui; Bao-Fu Zhao; Jin-An Wang; Yue-Qin Song; Xiao-Long Zhou (Environmental Science and Pollution Research, 2023)

Metal-organic framework (MOF)-based sensors for exogenous contaminants in food: Mechanisms, advances, and prospects - Wenjuan Wu; Ying Li; Pengyue Song; Qingbin Xu; Nan Long; Peng Li; Lidong Zhou; Bin Fu; Jiabo Wang; Weijun Kong (Trends in Food Science & Technology, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

Characteristics and load reduction method of the deep-sea implosion of the ellipsoidal and egg-shaped pressure hulls - Fu-Jin Yang; Yun-Long Liu; Shuai Zhang; Jun Guo (Ocean Engineering, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Effects of wildfire disturbance on forest soil microbes and colonization of ericoid mycorrhizal fungi in northern China - Hu Lou; Huiying Cai; Rao Fu; Chao Guo; Baozhen Fan; Haiqing Hu; Jie Zhang; Long Sun (Environmental Research, 2023)

Radon adsorption and air purification by Spanish moss (Tillandsia usneoides) and its metabolic response to radon exposure - Qian Fu; Jun-cheng Liang; Jin-long Lai; Xue-gang Luo (Environmental Pollution, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Magmatism and thermal effect of the Late Paleoproterozoic layered complex in the Jining terrane, North China Craton: Evidence from magmatic cooling duration and crust-mantle interaction - Wei-Peng Zhu; Wei Tian; Bin Wang; Ming-Yue Gong; Bin Fu; Zi-Long Wang; Chun-Jing Wei (Precambrian Research, 2023)

Revealing an unrecognized role of free ammonia in sulfur transformation during sludge anaerobic treatment - Qizi Fu; Sha Long; Yunhao Xu; Yan Wang; Bentao Yang; Dandan He; Xuemei Li; Xuran Liu; Qi Lu; Dongbo Wang (Journal of Hazardous Materials, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

Lanthanide bimetallic MOF-based fluorescent sensor for sensitive and visual detection of sulfamerazine and malachite - Xiaoyue Yue; Long Fu; Yan Li; Sheng Xu; Xin Lin; Yanhong Bai (Food Chemistry, 2023)

Study on the taste active compounds in Douchi using metabolomics method - Weidan Guo; Yu Zhang; Zhao Long; Xiangjin Fu; Kangzi Ren (Food Chemistry, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Amelioration of White Matter Injury Through Mitigating Ferroptosis Following Hepcidin Treatment After Spinal Cord Injury - Jiantao Shi; Xingsen Xue; Linbo Yuan; Guangjian He; Zhouyang Jiang; Long Wang; Jiali Zhang; Hong Su; Jishu Xian; Chuhua Fu; Shengli Hu (Molecular Neurobiology, 2023)

Plant growth strategy determines the magnitude and direction of drought‐induced changes in root exudates in subtropical forests - Zheng Jiang; Yuling Fu; Lingyan Zhou; Yanghui He; Guiyao Zhou; Peter Dietrich; Jilan Long; Xinxin Wang; Shuxian Jia; Yuhuang Ji; Zhen Jia; Bingqian Song; et al. (Global Change Biology, 2023)
Root exudates are an important pathway for plant–microbial interactions and are highly sensitive to climate change. However, how extreme drought affects root exudates and the main components, as well as species‐specific differences in response magnitude and direction, are poorly understood. In this study, root exudation rates of total carbon (C) and its components (e.g., sugar, organic acid, and amino acid) were measured under the control and extreme drought treatments (i.e., 70% throughfall reduction) by in situ collection of four tree species with different growth rates in a subtropical forest. We also quantified soil properties, root morphological traits, and mycorrhizal infection rates to examine the driving factors underlying variations in root exudation. Our results showed that extreme drought significantly decreased root exudation rates of total C, sugar, and amino acid by 17.8%, 30.8%, and 35.0%, respectively, but increased root exudation rate of organic acid by 38.6%, which were largely associated with drought‐induced changes in tree growth rates, root morphological traits, and mycorrhizal infection rates. Specifically, trees with relatively high growth rates were more responsive to drought for root exudation rates compared with those with relatively low growth rates, which were closely related to root morphological traits and mycorrhizal infection rates. These findings highlight the importance of plant growth strategy in mediating drought‐induced changes in root exudation rates. The coordinations among root exudation rates, root morphological traits, and mycorrhizal symbioses in response to drought could be incorporated into land surface models to improve the prediction of climate change impacts on rhizosphere C dynamics in forest ecosystems.

The Na+/H+ antiporter GbSOS1 interacts with SIP5 and regulates salt tolerance in Gossypium barbadense - Fu-Chun Xu; Mei-Juan Wang; Ya-Wei Guo; Jie Song; Wei Gao; Lu Long (Plant Science, 2023)

Investigation on diesel spray flame evolution and its conceptual model for large nozzle and high-density of ambient gas - Long Liu; Shiyi Fu; Changfu Han (Fuel, 2023)

Effect of foliar spraying of organic and inorganic selenium fertilizers during different growth stages on selenium accumulation and speciation in rice - Zhengqing Yuan; Weixiong Long; Ting Liang; Menghan Zhu; Aoyun Zhu; Xiaoyun Luo; Lu Fu; Zhongli Hu; Renshan Zhu; Xianting Wu (Plant and Soil, 2023)
Aims Most crops are supplemented with selenium (Se) through the exogenous addition of inorganic Se fertilizer. There is a lack of in-depth research on organic Se fertilizers. Meanwhile, the dosage range between human Se deficiency and Se toxicity is narrow, so the Se content of agricultural products needs to be controlled within a reasonable interval. Methods Se accumulation and speciation in rice were analyzed and compared during three different growth stages (late tillering stage, initiate heading stage, and full heading stage) using three Se fertilizers: selenite, fermented Se, and potassium selenocyanoacetate (Se-AAF) via the foliar application. Results The Se content in rice sprayed with organic Se fertilizer was controlled in the relatively safe range and met the human Se supplement requirement compared to the sprayed sodium selenite, which was too high of a dose. The percentage of organic Se and protein Se in brown rice was found to be similar in all three Se fertilizers. The highest organic Se content of 91.57% was found in the grain of rice at the full heading stage by spraying Se-AAF. The main Se species in the grain was selenomethionine (SeMet), which reached 80% of the total Se. Se-methyl selenocysteine(SeMeCys) was found only in Se-AAF. The grain quality showed that all three Se fertilizers increased the consistency of gelatinization. Conclusions Appropriately delaying the spraying time and selecting organic Se fertilizer as the Se source can help to produce green and safe selenium-rich rice.

Tacrolimus improved the pregnancy outcomes of patients with refractory recurrent spontaneous abortion and immune bias disorders: a randomized controlled trial - Juan Liu; Meiqin Li; Jinhua Fu; Guiling Yuan; Ning Li; Yinghui Fu; Long Zhao (European Journal of Clinical Pharmacology, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Competition between biogeochemical drivers and land-cover changes determines urban greening or browning - Long Li; Wenfeng Zhan; Weimin Ju; Josep Peñuelas; Zaichun Zhu; Shushi Peng; Xiaolin Zhu; Zihan Liu; Yuyu Zhou; Jiufeng Li; Jiameng Lai; Fan Huang; et al. (Remote Sensing of Environment, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Integrated effects of residual plastic films on soil-rhizosphere microbe-plant ecosystem - Fei Fu; Bibo Long; Qian Huang; Juanjuan Li; Weijun Zhou; Chong Yang (Journal of Hazardous Materials, 2023)

Benefits of mechanical weeding for weed control, rice growth characteristics and yield in paddy fields - Chuang Liu; Kaiqiang Yang; Yong Chen; Hao Gong; Xiao Feng; Zhenyu Tang; Dengbin Fu; Long Qi (Field Crops Research, 2023)

Denitrification efficiency, microbial communities and metabolic mechanisms of corn cob hydrolysate as denitrifying carbon source - Yingping Long; Yongwen Ma; Jinquan Wan; Yan Wang; Min Tang; Hao Fu; Jianye Cao (Environmental Research, 2023)

Comprehensive understanding of DOM reactivity in anaerobic fermentation of persulfate-pretreated sewage sludge via FT-ICR mass spectrometry and reactomics analysis - Jibao Liu; Chenlu Wang; Zhineng Hao; Gen Kondo; Manabu Fujii; Qing-Long Fu; Yuansong Wei (Water Research, 2023)

Modelling of paddy soil using the CFD-DEM coupling method - Zhenyu Tang; Hao Gong; Shuanglong Wu; Zhiwei Zeng; Zhiqi Wang; Yuhao Zhou; Dengbin Fu; Chuang Liu; Yinghu Cai; Long Qi (Soil and Tillage Research, 2023)

Bioaccumulation and emission of organophosphate esters in plants affecting the atmosphere's phosphorus cycle - Shengxing Long; Paul B. Hamilton; Bo Fu; Jing Xu; Luchao Han; Xinhao Suo; Yuqin Lai; Guofeng Shen; Fuliu Xu; Bengang Li (Environmental Pollution, 2023)

A highly efficient high-entropy metal hydroxymethylate electrocatalyst for oxygen evolution reaction - Qi Jiang; Ruihu Lu; Junfeng Gu; Long Zhang; Kailong Liu; Mengyan Huang; Peng Liu; Shiyu Zuo; Yilong Wang; Yan Zhao; Peiyan Ma; Zhengyi Fu (Chemical Engineering Journal, 2023)

Experimental and Numerical Investigations on Rock Breaking of TBM Disc Cutter Based on a Novel Platform with Rotational Cutting - Long-Chuan Deng; Fu-Bing Zhang; Xiao-Zhao Li; Chi Zhang; Yu-Kun Ji; Yun Wu (Rock Mechanics and Rock Engineering, 2023)

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Genesis and prospecting significance of the Buziwannan gold-polymetallic ore deposit in the West Kunlun Orogen Belt, China: Constraints from mineral geochemistry and in situ S–Pb isotope analyses of sulfides - Peiwen Chen; Qingdong Zeng; Lingli Zhou; Bing Liu; Yong Fu; Guotao Sun; Bing Yu; Zhen Long (Journal of Geochemical Exploration, 2023)

UHPLC-QTOF-MS-based untargeted metabolomics and mineral element analysis insight into the geographical differences of Chrysanthemum morifolium Ramat cv. “Hangbaiju” from different origins - Wanjun Long; Xiuyun Bai; Siyu Wang; Hengye Chen; Xiao-Li Yin; Hui-Wen Gu; Jian Yang; Haiyan Fu (Food Research International, 2023)

Bioinspired SiC aerogels for super thermal insulation and adsorption with super-elasticity over 100,000 times compressions - Mingyuan Yan; Xudong Cheng; Long Shi; Yuelei Pan; Pan He; Zhongxin Zhang; Zhiyi Lun; Yangyang Fu; Heping Zhang (Chemical Engineering Journal, 2023)

Catalytic hydrolysis of corncob for production of furfural and cellulose-rich solids: Product characterization and analysis - Bang Yao; Qinhao Kang; Jie Fu; Yang Liu; Wenya Ao; Long Wang; Zhihui Jiang; Tianhao Zhang; Yongmeng Song; Zeyu Deng; Asif Ali Siyal; Jianjun Dai (Biomass and Bioenergy, 2023)

Identification of tropical cyclone centre based on satellite images via deep learning techniques - Teng Long; Jiyang Fu; Biao Tong; Pakwai Chan; Yuncheng He (International Journal of Climatology, 2022)
A tropical cyclone (TC) is a highly destructive natural disaster. Accurate identification of key parameters of TCs is prerequisite for most TC‐related research and practices. The centre position is one of TC's basic parameters. However, comparison of TC best track data released by different meteorological institutes usually indicates a noticeable discrepancy for this parameter among varied data sources. In this study, efforts are made towards identifying the centre location of TCs via deep learning techniques, based on TC satellite cloud images (SCIs). Six deep learning models are analysed and compared. YOLOv4 model achieved a confidence of 99.84%, which is better than other models. In addition, we further explore the factors affecting the positioning accuracy of the YOLOv4 model and its application to the location identification of multiple TCs and the tracking of individual TCs. Results demonstrate that the YOLOv4 model has a probability exceeding 99% for identifying multiple TC locations and also performs well for single TC tracking.

Ecosystem Mercury Recovery and Health Benefit Under the Minamata Convention in a Changing Climate - Qingru Wu; Yanxu Zhang; Ping Li; Xuewu Fu; Qianggong Zhang; Xun Wang; Long Chen; Shuxiao Wang; Feiyue Wang; Xinbin Feng (Reviews of Environmental Contamination and Toxicology, 2022)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Analysis of water gushing after blockage of a drainage system in a deeply buried tunnel - Pengtao An; Helin Fu; Long Chen; Jie Li (Hydrogeology Journal, 2022)

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Application of an improved hollow fiber liquid phase microextraction technique coupled to LC-MS/MS to studying migration of fluorescent whitening agents from plastic food contact materials - Wen-Li Zhou; Li Ding; Yun-Hui Cheng; Zhou Xu; Mao-Long Chen; Xian-Shu Fu (Food Additives & Contaminants: Part A, 2022)

Establishment of a set of wheat-rye addition lines with resistance to stem rust - Chang Liu; Jing Wang; Shulan Fu; Long Wang; Hongwei Li; Mian Wang; Yuhong Huang; Qinghua Shi; Yonghong Zhou; Xianrui Guo; Congle Zhu; Jing Zhang; et al. (Theoretical and Applied Genetics, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Effect of particle distribution on the shear behavior of recycled concrete aggregate - Weihao Zhu; Jun Wang; Long Wang; Mengjie Ying; Xiuqing Hu; Hongtao Fu (Arabian Journal of Geosciences, 2022)

The association between environmental exposure to perchlorate, nitrate, and thiocyanate and all-cause and cause-specific mortality - Long Wang; Zhi Fu; Beibei Gao; Xuming Mo; Ping Liang; Jinyu Huang (Environmental Science and Pollution Research, 2022)

Role of Lysocardiolipin Acyltransferase in Cigarette Smoke-Induced Lung Epithelial Cell Mitochondrial ROS, Mitochondrial Dynamics, and Apoptosis - Mounica Bandela; Vidyani Suryadevara; Panfeng Fu; Sekhar P. Reddy; Kamesh Bikkavilli; Long Shuang Huang; Sugasini Dhavamani; Papasani V. Subbaiah; Sunit Singla; Steven M. Dudek; Lorraine B. Ware; Ramaswamy Ramchandran; et al. (Cell Biochemistry and Biophysics, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Research and application of a comprehensive forecasting system for tunnels in water-bearing fault fracture zones: a case study - Chang-fu Huang; Shuai-long Zhang; Shun-chuan Wu; Yong-tao Gao (Arabian Journal of Geosciences, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Retraction Note: Tropical coastal climate change based on image defogging algorithm and swimming rehabilitation training - Lijun Long; Yanqing Fu; Long Xiao (Arabian Journal of Geosciences, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China - Yan‐Zhen Zhang; Qing‐Dian Han; Long‐Wei Fu; Yong‐Xing Wang; Zhi‐Hai Sui; Yun‐Guo Liu (Journal of Fish Biology, 2021)
The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection rate to fish eggs. Based on internal transcribed spacer sequence data and molecular analysis, the 26 strains were classified into nine different species of six fungal genera. Phylogenetic analysis showed that all strains were divided into two clades, namely Cluster 1 (contains only the genus Mucor ) and Cluster 2 (consists of five small branches), and the distribution of strains from the same region was scattered in two clusters. There is no strict host selectivity for these fungi to infect fish. Mucor sp. are the main fungal pathogen of fish in these four regions, whereas Hypophthalmichthys molitrix and Carassius auratus are two types of fish that were susceptible to pathogen. In addition, the environmental adaptability experiments showed that eight highly pathogenic strains have different adaptability to the environment, and their optimum temperature and pH were 25°C and 7.0, respectively, whereas the concentration of NaCl was negatively correlated with the growth of strains. Therefore, these results indicated that the coinfection of multiple fungal pathogens in a culture region should be considered in the future study.

Reliability of the prediction model for landslide displacement with step-like behavior - Zhiyong Fu; Jingjing Long; Wenqiang Chen; Changdong Li; Haikuan Zhang; Wenmin Yao (Stochastic Environmental Research and Risk Assessment, 2021)

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

RETRACTED ARTICLE: Tropical coastal climate change based on image defogging algorithm and swimming rehabilitation training - Lijun Long; Yanqing Fu; Long Xiao (Arabian Journal of Geosciences, 2021)

A novel model for regional susceptibility mapping of rainfall-reservoir induced landslides in Jurassic slide-prone strata of western Hubei Province, Three Gorges Reservoir area - Jingjing Long; Yong Liu; Changdong Li; Zhiyong Fu; Haikuan Zhang (Stochastic Environmental Research and Risk Assessment, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Genome-wide association mapping for resistance to bacterial blight and bacterial leaf streak in rice - Nan Jiang; Jun Fu; Qin Zeng; Yi Liang; Yanlong Shi; Zhouwei Li; Youlun Xiao; Zhizhou He; Yuntian Wu; Yu Long; Kai Wang; Yuanzhu Yang; et al. (Planta, 2021)

Cytological and morphology characteristics of natural microsporogenesis within Camellia oleifera - Xiaoyu Zhang; Hailang Tong; Zhiqiang Han; Long Huang; Jing Tian; Zhixing Fu; Yunyi Wu; Ting Wang; Deyi Yuan (Physiology and Molecular Biology of Plants, 2021)

Stable isotopes and chloride ion of precipitation events in the northeastern Tibetan Plateau, China - Bu-li Cui; Dong-sheng Li; Bao-fu Jiang; Ying Wang; Ya-xuan Wang; Long-sheng Wang; Xiao-yan Li (Journal of Mountain Science, 2021)

Paraphyly of the genus Boehmeria (Urticaceae): a response to Liang et al. ‘Relationships among Chinese Boehmeria species and the evolution of various clade’ - Alexandre K. Monro; Steven Dodsworth; Long-Fei Fu; Ib Friis; Christine M. Wilmot-Dear; Olivier Maurin (Plant Systematics and Evolution, 2021)
Boehmeria , as currently circumscribed, comprises 52 species and has a pantropical distribution. Liang et al. propose a sectional classification of Boehmeria based on the phylogenetic analysis of SNP data for 20 species and an additional 10 subspecific taxa of these at the rank of variety or form. They restrict their sampling to species documented in China. We found many shortcomings in the sampling and analyses which we feel have resulted in a misleading phylogeny for the genus and the economically important fibre-plant, Boehmeria nivea . By sampling only Chinese species of this genus for their in-group and using a single distantly related outgroup, Liang et al. have failed to capture the diversity of the genus and so erroneously concluded that it forms a monophyletic group. Previous published research clearly demonstrates that Boehmeria is paraphyletic and polyphyletic, comprising at least four monophyletic groupings most closely related to several genera within the Boehmerieae. For these reasons, the sections that Liang et al. (Ind Crops Prod 148:112092, 2020. https://doi.org/10.1016/j.indcrop.2020.112092) propose for Boehmeria are not effective tools for its classification. The important fibre-plant, Boehmeria nivea , should therefore not be considered as part of the genus Boehmeria for the purposes of crop breeding, but as sister to Archiboehmeria . Breeding programmes for ramie should therefore focus on populations and germplasm of Archiboehmeria atrata . We conclude that poor taxon sampling, overlooking relevant molecular and taxonomic literature, internal conflict within their SNP data and the overinterpretation of low support values has resulted in the erroneous conclusion that Boehmeria represents a monophyletic or ‘natural’ genus.

Comparative proteomic analysis of parasitic loranthus seeds exposed to dehydration stress - Limei Pan; Lingyun Wan; Lili He; Lisha Song; Hairong Long; Xiaowen Ji; Ni Jiang; Juan Huo; Shugen Wei; Jine Fu (Plant Biotechnology Reports, 2021)

Construction and characterization of an infectious cDNA clone of enterovirus 71: a rapid method for rescuing infectious virus based on stable cells expressing T7 polymerase - Meixian Fu; Jinjin Bai; Shuang Gao; Zhangmei Chang; Xin Zhou; Jian-Er Long (Archives of Virology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Correction to: A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2021)

Dynamic Change of Shanks Gene mRNA Expression and DNA Methylation in Epileptic Rat Model and Human Patients - Yujiao Fu; Du Liu; Jialing Guo; Hongyu Long; Wenbiao Xiao; Wei Xiao; Li Feng; Zhaohui Luo; Bo Xiao (Molecular Neurobiology, 2020)

AMPKα2 deficiency exacerbates hypoxia-induced pulmonary hypertension by promoting pulmonary arterial smooth muscle cell proliferation - Hai-Long Wang; Fu-Qin Tang; Yun-Han Jiang; Yu Zhu; Zhao Jian; Ying-Bin Xiao (Journal of Physiology and Biochemistry, 2020)

Genesis of baddeleyite and high δ18O zircon in impure marble from the Tongbai orogen, Central China: insights from petrochronology and Hf–O isotope compositions - Guangyan Zhou; Yuanbao Wu; Bin Fu; Long Li; Wen-Xiang Zhang; Yelv Zhang (Contributions to Mineralogy and Petrology, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Building a sequence map of the pig pan-genome from multiple de novo assemblies and Hi-C data - Xiaomeng Tian; Ran Li; Weiwei Fu; Yan Li; Xihong Wang; Ming Li; Duo Du; Qianzi Tang; Yudong Cai; Yiming Long; Yue Zhao; Mingzhou Li; et al. (Science China Life Sciences, 2020)

Correction to: Nucleoporin Nup98 participates in flowering regulation in a CONSTANS-independent mode - Shanshan Jiang; Long Xiao; Penghui Huang; Zhiyuan Cheng; Fulu Chen; Yuchen Miao; Yong-Fu Fu; Qingshan Chen; Xiao-Mei Zhang (Plant Cell Reports, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Major advances in studies of the physical geography and living environment of China during the past 70 years and future prospects - Fahu Chen; Bojie Fu; Jun Xia; Duo Wu; Shaohong Wu; Yili Zhang; Hang Sun; Yu Liu; Xiaomin Fang; Boqiang Qin; Xin Li; Tingjun Zhang; et al. (Science China Earth Sciences, 2019)

Nucleoporin Nup98 participates in flowering regulation in a CONSTANS-independent mode - Shanshan Jiang; Long Xiao; Penghui Huang; Zhiyuan Cheng; Fulu Chen; Yuchen Miao; Yong-Fu Fu; Qingshan Chen; Xiao-Mei Zhang (Plant Cell Reports, 2019)

Protective Effects of 1-Methylnicotinamide on Aβ1–42-Induced Cognitive Deficits, Neuroinflammation and Apoptosis in Mice - Lili Fu; Caihong Liu; Liang Chen; Yangge Lv; Guoliang Meng; Mei Hu; Yan Long; Hao Hong; Susu Tang (Journal of Neuroimmune Pharmacology, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Late Cretaceous magmatism and porphyry Mo–Cu polymetallic mineralization in the Tongchanggou Intrusion, Geza Arc, Southwestern China - Xue-long Liu; Jian-hang Chen; Wen-chang Li; Na Zhang; Shuai-shuai Wang; Chang-zhen Zhang; Ying Luo; Zhen-huan Li; Fu-cheng Yang (Arabian Journal of Geosciences, 2019)

A Highly Selective Fluorescence “Turn on” and Absorbance-Ratiometric Detection of Al3+ in Totally H2O and its Application in Test Paper - Xue-Jiao Sun; Yu-Qing Ma; Hong Fu; Zhi-Yong Xing; Zhi-Gang Sun; Yue Shen; Jin-Long Li (Journal of Fluorescence, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Evoked potential study of the inferior collicular response to constant frequency-frequency modulation (CF-FM) sounds in FM and CF-FM bats - Ziying Fu; Na Xu; Guimin Zhang; Dandan Zhou; Long Liu; Jia Tang; Philip Hung-Sun Jen; Qicai Chen (Journal of Comparative Physiology A, 2019)

Effects of acclimation temperature on the thermal tolerance, hypoxia tolerance and swimming performance of two endangered fish species in China - Long-Yan Zhou; Shi-Jian Fu; Cheng Fu; Hong Ling; Xiu-Ming Li (Journal of Comparative Physiology B, 2019)

Physiological responses of the freshwater N 2 ‐fixing cyanobacterium Raphidiopsis raciborskii to Fe and N availabilities - Qing‐Long Fu; Anna C. Y. Yeung; Manabu Fujii; Brett A. Neilan; T. David Waite (Environmental Microbiology, 2019)
Summary The cyanobacterium Raphidiopsis raciborskii is of environmental and social concern in view of its toxicity, bloom‐forming characteristics and increasingly widespread occurrence. However, while availability of macronutrients and micronutrients such as N and Fe are critically important for the growth and metabolism of this organism, the physiological response of toxic and non‐toxic strains of R. raciborskii to varying Fe and N availabilities remains unclear. By determining physiological parameters as a function of Fe and N availability, we demonstrate that R. raciborskii growth and N 2 ‐fixing activity are facilitated at higher Fe availability under N 2 ‐limited conditions with faster growth of the CS‐506 (cylindrospermopsin‐producing) strain compared with that of CS‐509 (the non‐toxic) strain. Radiolabelled Fe uptake assays indicated that R. raciborskii acclimated under Fe‐limited conditions acquires Fe at significantly higher rates than under Fe replete conditions, principally via unchelated Fe(II) generated as a result of photoreduction of complexed Fe(III). While N 2 ‐fixation of both strains occurred during both day and night, the CS‐506 strain overall exhibited higher N 2 ‐fixing and Fe uptake rates than the CS‐509 strain under N‐deficient and Fe‐limited conditions. The findings of this study highlight that Fe availability is of significance for the ecological advantage of CS‐506 over CS‐509 in N‐deficient freshwaters.

Centrifugal model tests and numerical simulations for barrier dam break due to overtopping - Tian-long Zhao; Sheng-shui Chen; Chang-jing Fu; Qi-ming Zhong (Journal of Mountain Science, 2019)

Meteorological conditions during a severe, prolonged regional heavy air pollution episode in eastern China from December 2016 to January 2017 - Xueliang Deng; Weihua Cao; Yanfeng Huo; Guanying Yang; Caixia Yu; Dongyan He; Weitao Deng; Wei Fu; Heming Ding; Jing Zhai; Long Cheng; Xuhui Zhao (Theoretical and Applied Climatology, 2019)

Orientation Behavior and Regulatory Gene Expression Profiles in Migratory Agrotis ipsilon (Lepidoptera: Noctuidae) - Hong Chang; Jiang Long Guo; Xiao Wei Fu; You Ming Hou; Kong Ming Wu (Journal of Insect Behavior, 2019)

Cytotoxic indole alkaloids from Nauclea orientalis - Yan-Ping Liu; Peng-Kun Ju; Jin-Tao Long; Liang Lai; Wan-Hui Zhao; Chao Zhang; Zhi-Jie Zhang; Yan-Hui Fu (Natural Product Research, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Silencing of GbANS reduces cotton resistance to Verticillium dahliae through decreased ROS scavenging during the pathogen invasion process - Lu Long; Jing-Ruo Zhao; Fu-Chun Xu; Wen-Wen Yang; Peng Liao; Ya Gao; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Microbial transformation of resveratrol by endophyte Streptomyces sp. A12 isolated from Polygonum cuspidatum - Tian Jiewei; Wang Lei; Long Xiufeng; Zhang Heming; Li Xiaoguang; Fu Haiyan; Tian Yongqiang (Natural Product Research, 2018)

Low methane emission in rice cultivars with high radial oxygen loss - Huabin Zheng; Zhiqiang Fu; Juan Zhong; Wenfei Long (Plant and Soil, 2018)

Lacidipine Amorphous Solid Dispersion Based on Hot Melt Extrusion: Good Miscibility, Enhanced Dissolution, and Favorable Stability - Long Xi; Hang Song; Yunzhi Wang; Haoshi Gao; Qiang Fu (AAPS PharmSciTech, 2018)

From State-controlled to Polycentric Governance in Forest Landscape Restoration: The Case of the Ecological Forest Purchase Program in Yong’an Municipality of China - Hexing Long; Jinlong Liu; Chengyue Tu; Yimin Fu (Environmental Management, 2018)

Novel method for iron recovery from hazardous iron ore tailing with induced carbothermic reduction-magnetic flocculation separation - Shao-Jun Bai; Chun-Long Li; Xiang-Yu Fu; Chao Lv; Shu-Ming Wen (Clean Technologies and Environmental Policy, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Anti-complementary constituents of Viola kunawarensis - Hui Wang; Wen-Li Cong; Ze-long Fu; Dao-Feng Chen; Qi Wang (Natural Product Research, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Tolerance and stress response of sclerotiogenic Aspergillus oryzae G15 to copper and lead - Dan-Dan Long; Rong-Rong Fu; Jian-Rong Han (Folia Microbiologica, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Landscape dynamics and driving forces of wetlands in the Tumen River Basin of China over the past 50 years - Xiao Jun Zheng; Peng Sun; Wei Hong Zhu; Zhen Xu; Jing Fu; Wei Dong Man; Hai Long Li; Jian Zhang; Lei Qin (Landscape and Ecological Engineering, 2017)

Debris flows monitoring and localization using infrasonic signals - Xiao-peng Leng; Dun-long Liu; Fang-qiang Wei; Yong Hong; De-fu Dai (Journal of Mountain Science, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Geochemistry and petrogenesis of Triassic mineralized porphyries in the Geza of the Sanjiang orogenic belt, southwestern China - Xue-long Liu; Wen-chang Li; Na Zhang; Fu-cheng Yang (International Geology Review, 2017)

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Perfluoroalkyl substances with isomer analysis in umbilical cord serum in China - Ya-Zhi Zhang; Xiao-Wen Zeng; Zhengmin Qian; Michael G. Vaughn; Sarah Dee Geiger; Li-Wen Hu; Long Lu; Chuanxi Fu; Guang-Hui Dong (Environmental Science and Pollution Research, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Cultivated land information extraction in UAV imagery based on deep convolutional neural network and transfer learning - Heng Lu; Xiao Fu; Chao Liu; Long-guo Li; Yu-xin He; Nai-wen Li (Journal of Mountain Science, 2017)

Endovascular Treatment Versus Intravenous Thrombolysis for Acute Ischemic Stroke: a Quantitative Review and Meta-Analysis of 21 Randomized Trials - Chen-Chen Tan; Hui-Fu Wang; Jin-Long Ji; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Brain Development and Akt Signaling: the Crossroads of Signaling Pathway and Neurodevelopmental Diseases - Long Wang; Kai Zhou; Zhi Fu; Di Yu; Hesuyuan Huang; Xiaodong Zang; Xuming Mo (Journal of Molecular Neuroscience, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Frequency specific brain networks in Parkinson’s disease and comorbid depression - Long Qian; Yi Zhang; Li Zheng; Xuemei Fu; Weiguo Liu; Yuqing Shang; Yaoyu Zhang; Yuanyuan Xu; Yijun Liu; Huaiqiu Zhu; Jia-Hong Gao (Brain Imaging and Behavior, 2017)

Tornado hazards on June 23 in Jiangsu Province, China: preliminary investigation and analysis - Hai-Min Lyu; Guo-Fu Wang; Wen-Chieh Cheng; Shui-Long Shen (Natural Hazards, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Extraction and speciation analysis of roxarsone and its metabolites from soils with different physicochemical properties - Qing-Long Fu; Jian-Zhou He; Hua Gong; Lee Blaney; Dong-Mei Zhou (Journal of Soils and Sediments, 2016)

Recombinant infectious bronchitis virus (IBV) H120 vaccine strain expressing the hemagglutinin-neuraminidase (HN) protein of Newcastle disease virus (NDV) protects chickens against IBV and NDV challenge - Xin Yang; Yingshun Zhou; Jianan Li; Li Fu; Gaosheng Ji; Fanya Zeng; Long Zhou; Wenqian Gao; Hongning Wang (Archives of Virology, 2016)

First Oligocene mummified plant Lagerstätte at the low latitudes of East Asia - Cheng Quan; QiongYao Fu; GongLe Shi; YuSheng Liu; Long Li; XiaoYan Liu; JianHua Jin (Science China Earth Sciences, 2016)

A systematic approach to expound the variations in taxane production under different dissolved oxygen conditions in Taxus chinensis cells - Chunfang Zhao; Guanghao Song; Chunhua Fu; Yanshan Dong; Hang Xu; Hua Zhang; Long Jiang Yu (Plant Cell Reports, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Effects of induced pluripotent stem cells-derived conditioned medium on the proliferation and anti-apoptosis of human adipose-derived stem cells - Rui-Ling Lian; Xiao-Ling Guo; Jian-Su Chen; Yong-Long Guo; Jia-Fu Zheng; Yuan-Wen Chen (Molecular and Cellular Biochemistry, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

NMR-Based Metabolic Profiling Reveals Neurochemical Alterations in the Brain of Rats Treated with Sorafenib - Changman Du; Xue Shao; Ruiming Zhu; Yan Li; Qian Zhao; Dengqi Fu; Hui Gu; Jueying Kong; Li Luo; Hailei Long; Pengchi Deng; Huijuan Wang; et al. (Neurotoxicity Research, 2015)

Production of sweet orange somaclones tolerant to citrus canker disease by in vitro mutagenesis with EMS - Hongjuan Ge; Yi Li; Hongyan Fu; Guiyou Long; Li Luo; Ronghua Li; Ziniu Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Generation by reverse genetics of an effective attenuated Newcastle disease virus vaccine based on a prevalent highly virulent Chinese strain - Meng-Meng Liu; Jin-Long Cheng; Xiao-Hui Yu; Zhuo-Ming Qin; Fu-Lin Tian; Guo-Zhong Zhang (Biotechnology Letters, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

A comparison of the potential health risk of aluminum and heavy metals in tea leaves and tea infusion of commercially available green tea in Jiangxi, China - Lanhai Li; Qing-Long Fu; Varenyam Achal; Yonglin Liu (Environmental Monitoring and Assessment, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Isolation and characterization of an ubiquitin extension protein gene (JcUEP) promoter from Jatropha curcas - Yan-Bin Tao; Liang-Liang He; Long-Jian Niu; Zeng-Fu Xu (Planta, 2015)

Intercropping enhances soil carbon and nitrogen - Wen‐Feng Cong; Ellis Hoffland; Long Li; Johan Six; Jian‐Hao Sun; Xing‐Guo Bao; Fu‐Suo Zhang; Wopke Van Der Werf (Global Change Biology, 2015)
Intercropping, the simultaneous cultivation of multiple crop species in a single field, increases aboveground productivity due to species complementarity. We hypothesized that intercrops may have greater belowground productivity than sole crops, and sequester more soil carbon over time due to greater input of root litter. Here, we demonstrate a divergence in soil organic carbon (C) and nitrogen (N) content over 7 years in a field experiment that compared rotational strip intercrop systems and ordinary crop rotations. Soil organic C content in the top 20 cm was 4% ± 1% greater in intercrops than in sole crops, indicating a difference in C sequestration rate between intercrop and sole crop systems of 184 ± 86 kg C ha −1 yr −1 . Soil organic N content in the top 20 cm was 11% ± 1% greater in intercrops than in sole crops, indicating a difference in N sequestration rate between intercrop and sole crop systems of 45 ± 10 kg N ha −1 yr −1 . Total root biomass in intercrops was on average 23% greater than the average root biomass in sole crops, providing a possible mechanism for the observed divergence in soil C sequestration between sole crop and intercrop systems. A lowering of the soil δ 15 N signature suggested that increased biological N fixation and/or reduced gaseous N losses contributed to the increases in soil N in intercrop rotations with faba bean. Increases in soil N in wheat/maize intercrop pointed to contributions from a broader suite of mechanisms for N retention, e.g., complementary N uptake strategies of the intercropped plant species. Our results indicate that soil C sequestration potential of strip intercropping is similar in magnitude to that of currently recommended management practises to conserve organic matter in soil. Intercropping can contribute to multiple agroecosystem services by increased yield, better soil quality and soil C sequestration.

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Isolation and characterization of microsatellite markers in the Asiatic water snake (Xenochrophis piscator) - Zong-Shi Zhou; Tian-Long Fu; Chao-Nan Zhu; Shan Sun; Yan-Fu Qu (Conservation Genetics Resources, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Genetic analysis of litchi (Litchi chinensis Sonn.) in southern China by improved random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) - Yan Long; Jingliang Cheng; Zhiqiang Mei; Ling Zhao; Chunli Wei; Shelly Fu; Md. Asaduzzaman Khan; Junjiang Fu (Molecular Biology Reports, 2015)

Distribution of metals and brominated flame retardants (BFRs) in sediments, soils and plants from an informal e-waste dismantling site, South China - Junxia Wang; Lili Liu; Jinfu Wang; Bishu Pan; Xiaoxu Fu; Gang Zhang; Long Zhang; Kuangfei Lin (Environmental Science and Pollution Research, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Identification and characterization of a novel phage display-derived peptide with affinity for human brain metastatic breast cancer - Bo Fu; Ying Zhang; Wei Long; Aifeng Zhang; Yafen Zhang; Yanli An; Fengqin Miao; Fang Nie; Mingli Li; Youji He; Jianqiong Zhang; Gaojun Teng (Biotechnology Letters, 2014)

Numerical Analysis of Surface Runoff for the Liudaogou Drainage Basin in the North Loess Plateau, China - Qiang Fu; Long-Bin Lu; Jin-Bai Huang (Water Resources Management, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

Crosstalk between TGF-β1 and CXCR3 signaling during urethral fibrosis - Hong Xie; Chao Feng; Qiang Fu; Ying-Long Sa; Yue-Min Xu (Molecular and Cellular Biochemistry, 2014)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

Isolation and characterization of microsatellite loci in the endangered Amur ratsnake Elaphe schrenckii (Reptilia; Squamata; Colubridae) from China - Xue-yang Xu; Tian-long Fu; Yan-Fu Qu; Xiao-xiao Zheng; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

Isolation and characterization of phosphate-solubilizing bacteria from betel nut (Areca catechu) and their effects on plant growth and phosphorus mobilization in tropical soils - Fu-Ping Liu; Hai-Qing Liu; Hai-Long Zhou; Zhi-Guo Dong; Xu-Hao Bai; Peng Bai; Jian-Jun Qiao (Biology and Fertility of Soils, 2014)

Constructing a dense genetic linkage map and mapping QTL for the traits of flower development in Brassica carinata - Jun Zou; Harsh Raman; Shaomin Guo; Dandan Hu; Zili Wei; Ziliang Luo; Yan Long; Wenxia Shi; Zhong Fu; Dezhi Du; Jinling Meng (Theoretical and Applied Genetics, 2014)

Co-delivery of Dexamethasone and Green Tea Polyphenols Using Electrospun Ultrafine Fibers for Effective Treatment of Keloid - Jinrong Li; Rong Fu; Long Li; Guang Yang; Shan Ding; Zhendong Zhong; Shaobing Zhou (Pharmaceutical Research, 2014)

Antithrombotic Peptides from Scolopendra subspinipes mutilans Hydrolysates - Yi Kong; Shuai Li; Yu Shao; Zhi-long He; Mei-mei Chen; Xin Ming; Ji-fu Wei (International Journal of Peptide Research and Therapeutics, 2014)

A survey on the heavy metal contents in Chinese traditional egg products and their potential health risk assessment - Qing-long Fu; Yonglin Liu; Lanhai Li; Varenyam Achal (Food Additives & Contaminants Part B-Surveillance, 2014)

Sustained endoplasmic reticulum stress inhibits hepatocyte proliferation via downregulation of c-Met expression - Yihuai He; Jun Long; Weiwei Zhong; Yu Fu; Ying Li; Shide Lin (Molecular and Cellular Biochemistry, 2014)

Modeling of spatial distributions of farmland density and its temporal change using geographically weighted regression model - Haitao Zhang; Long Guo; Jiaying Chen; Peihong Fu; Jianli Gu; Guangyu Liao (Chinese Geographical Science, 2014)

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

Yeast-Incorporated Gallium Attenuates Glucocorticoid-Induced Bone Loss in Rats by Inhibition of Bone Resorption - Zhaozhou Ren; Liqing Yang; Feng Xue; Qingjie Meng; Kejia Wang; Xian Wu; Chao Ji; Teng Jiang; Da Liu; Long Zhou; Jing Zhang; Qin Fu (Biological Trace Element Research, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Investigation of the relationship between chromobox homolog 8 and nucleus pulposus cells degeneration in rat intervertebral disc - Xu Zhou; Hai-Long Zhang; Guang-Fei Gu; Yue Ding; Jian-Bo Jia; Qing-Song Fu; Shi-Sheng He (In Vitro Cellular & Developmental Biology - Animal, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Testis specific serine/threonine kinase 4 (Tssk4) maintains its kinase activity by phosphorylating itself at Thr-197 - Youheng Wei; Xiaoli Wang; Guolong Fu; Long Yu (Molecular Biology Reports, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Drought-induced proline accumulation is uninvolved with increased nitric oxide, which alleviates drought stress by decreasing transpiration in rice - Jie Xiong; Long Zhang; Guanfu Fu; Yongjie Yang; Cheng Zhu; Longxing Tao (Journal of Plant Research, 2012)

The Potential Influence of Seasonal Climate Variables on the Net Primary Production of Forests in Eastern China - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Jin Long Zhang (Environmental Management, 2011)

Semi-supervised joint spatio-temporal feature selection for P300-based BCI speller - Jinyi Long; Zhenghui Gu; Yuanqing Li; Tianyou Yu; Feng Li; Ming Fu (Cognitive Neurodynamics, 2011)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Molecular authentication of geo-authentic Scrophularia ningpoensis - Chuan Chen; Li-na Duan; Xiao-long Zhou; Bing-long Chen; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2011)

Overyielding and interspecific interactions mediated by nitrogen fertilization in strip intercropping of maize with faba bean, wheat and barley - Qiu-Zhu Li; Jian-Hao Sun; Xiao-Jing Wei; Peter Christie; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Expression of stromal derived factor-1 (SDF-1) and chemokine receptor (CXCR4) in bone metastasis of renal carcinoma - Fu-long Zhao; Wei Guo (Molecular Biology Reports, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

The reversed terminator of octopine synthase gene on the Agrobacterium Ti plasmid has a weak promoter activity in prokaryotes - Jun-Li Shao; Yue-Sheng Long; Gu Chen; Jun Xie; Zeng-Fu Xu (Molecular Biology Reports, 2010)

Multiple shoots induction in wild cotton (Gossypium bickii) through organogenesis and the analysis of genetic homogeneity of the regenerated plants - Xi-Yan Yang; Xian-Long Zhang; Li-Li Fu; Ling Min; Guan-ze Liu (Biologia, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Role of Diverse Non-Systemic Fungal Endophytes in Plant Performance and Response to Stress: Progress and Approaches - Zhi-lin Yuan; Chu-long Zhang; Fu-cheng Lin (Journal of Plant Growth Regulation, 2010)

An improved nitrogen difference method for estimating biological nitrogen fixation in legume-based intercropping systems - Chang-Bing Yu; Yu-Ying Li; Chun-Jie Li; Jian-Hao Sun; X. H. He; Fu-Suo Zhang; Long Li (Biology and Fertility of Soils, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

Nonlinear continuum of egg size-number trade-offs in a snake: is egg-size variation fitness related? - Xiang Ji; Wei-Guo Du; Yan-Fu Qu; Long-Hui Lin (Oecologia, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Host‐associated speciation in the coral barnacle Wanella milleporae (Cirripedia: Pyrgomatidae) inhabiting the Millepora coral - LING MING TSANG; BENNY KWOK KAN CHAN; FU‐LONG SHIH; KA HOU CHU; CHAOLUN ALLEN CHEN (Molecular Ecology, 2009)
Speciation by host shift is a common phenomenon observed in many symbiotic animals. The symbiont–host interaction is highly dynamic, but it is poorly documented in the marine realm. In the present study, we examined the genetic and morphological differentiation of the coral barnacle Wanella milleporae (obligate to fire corals) collected from four different Millepora host species in Taiwan to investigate the host specificity of this barnacle. Phylogenetic analysis of mitochondrial COI gene for 241 individuals of Wanella revealed five distinct clades, whose sequence divergences are comparable to values between other cogeneric barnacle species. The five clades also differ in shell and opercular plate morphology and colour. Genetic and morphological differentiations together strongly suggest the presence of cryptic species. Although the five clades do not display species‐level host specificity, they showed a significant difference in preference on host growth form. Clades 1 and 2 were predominantly found on encrusting Millepora exaesa and Millepora platyphylla , while clades 3, 4 and 5 live exclusively on branching‐form fire corals Millepora dichotoma and Millepora tenella . Phylogeny inferred from the combined mitochondrial COI, 16S and 12S (2182 bp) analysis suggests the division of the five clades into two major lineages congruent with the morphology of the host coral. Multiple independent invasions to the same form of host and subsequent speciation are evident in the Red Sea and Taiwan. Our results indicate that ecological/sympatric speciation could occur in marine symbiotic invertebrates through host shift and specialization. It appears that, as in their terrestrial counterparts, host–symbiont radiations in the marine realm are more prevalent than we expected and thus warrant further investigation.

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

Specific leaf area relates to the differences in leaf construction cost, photosynthesis, nitrogen allocation, and use efficiencies between invasive and noninvasive alien congeners - Yu-Long Feng; Gai-Lan Fu; Yu-Long Zheng (Planta, 2008)

Nitrogen allocation, partitioning and use efficiency in three invasive plant species in comparison with their native congeners - Yu-Long Feng; Gai-Lan Fu (Biological Invasions, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

Genetic Diversity and Geographic Differentiation in the Threatened Species Dysosma pleiantha in China as Revealed by ISSR Analysis - Min Zong; Hai-Long Liu; Ying-Xiong Qiu; Shu-Zhen Yang; Ming-Shui Zhao; Cheng-Xin Fu (Biochemical Genetics, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Identification of functional candidate genes for drought tolerance in rice - Bin-Ying Fu; Jian-Hua Xiong; Ling-Hua Zhu; Xiu-Qin Zhao; Hua-Xue Xu; Yong-Ming Gao; Yang-Sheng Li; Jian-Long Xu; Zhi-Kang Li (Molecular Genetics and Genomics, 2007)

Generation and characterization of two novel low phytate mutations in soybean (Glycine max L. Merr.) - Feng-Jie Yuan; Hai-Jun Zhao; Xue-Liang Ren; Shen-Long Zhu; Xu-Jun Fu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Production and characterization of asymmetric hybrids between upland cotton Coker 201 (Gossypium hirsutum) and wild cotton (G. klozschianum Anderss) - Xi-yan Yang; Xian-long Zhang; Shuang-xia Jin; Li-li Fu; Ling-gang Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Generation and characterization of low phytic acid germplasm in rice (Oryza sativa L.) - Qing-Long Liu; Xiu-Hong Xu; Xue-Liang Ren; Hao-Wei Fu; Dian-Xing Wu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Supplementary data: Assessment of genetic diversity ofLycoris longituba (Amaryllidaceae) detected by RAPDs - Chuan-Liang Deng; Jian Zhou; Wu-Jun Gao; Fu-Cong Sun; Rui-Yun Qin; Long-Dou Lu (Journal of Genetics, 2006)

Study of removal effect on Mesocyclops leukarti with oxidants - Jin-long Zuo; Fu-yi Cui; Tao Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Relationship between double product break point, lactate threshold, and ventilatory threshold in cardiac patients - Kazuto Omiya; Haruki Itoh; Naomi Harada; Tomoko Maeda; Akihiko Tajima; Keiko Oikawa; Akira Koike; Tadanori Aizawa; Long-Tai Fu; Naohiko Osada (European Journal of Applied Physiology, 2004)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Structure characterization of human RalGDS gene, and the identification of its novel variant - Qiping Zheng; Long Yu; Yong Zhao; Honglai Zhang; Qiang Fu; Ninghui Mao; Peirong Hu; Zhencheng Geng; Shouyuan Zhao (Molecular Biology Reports, 2000)

Cloning, tissue expression pattern and genomic organization of latexin, a human homologue of rat carboxypeptidase A inhibitor - Qing Liu; Long Yu; Jie Gao; Qiang Fu; Jianxuan Zhang; Pingzhao Zhang; Jian Chen; Shouyuan Zhao (Molecular Biology Reports, 2000)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)

Molecular Cloning and Tissue Expression Analysis of the β Subunit of Elongation Factor 1 in the Mouse - Qing Liu; Long Yu; Qiang Fu; Tieming Lang; Jianxuan Zhang; Daqin Mao; Shouyuan Zhao (Biochemical Genetics, 2000)

Genetic Diversity of Cattle in South China as Revealed by Blood Protein Electrophoresis - Long Nie; Ying Yu; Xi-Quan Zhang; Guan-Fu Yang; Ji-Kun Wen; Ya-Ping Zhang (Biochemical Genetics, 1999)